Polypropylene-based foamed particles and polypropylene-based foamed molded bodies, and methods for producing the same

CN117083324BActive Publication Date: 2026-10-27KANEKA CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202280023237.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-03-26
Filing Date
2022-03-25
Publication Date
2026-10-27
Estimated Expiration
2042-03-25

AI Technical Summary

Benefits of technology

[0015]根据本发明的一个实施方式,起到如下效果:与现有技术相比,可提供能够提供阻燃性更优异的聚丙烯系发泡成型体的聚丙烯系发泡颗粒。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0004460724940000101
    Figure GDA0004460724940000101
  • Figure GDA0004460724940000102
    Figure GDA0004460724940000102
  • Figure GDA0004460724940000111
    Figure GDA0004460724940000111
Patent Text Reader

Abstract

To provide polypropylene-based foaming particles capable of providing a foaming molded body having excellent flame retardancy. The foregoing problem is solved by polypropylene-based foaming particles containing a polypropylene-based resin (A), an organic phosphorus-based compound (B), and a hindered amine (C), containing, relative to 100% by weight of the total amount of the polypropylene-based foaming particles, more than 10.0% by weight and 20.0% by weight or less of the organic phosphorus-based compound (B), and 1.0% by weight to 10.0% by weight of the hindered amine (C).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to polypropylene foamed granules and polypropylene foamed molded articles, as well as methods for manufacturing them. Background Technology

[0002] Foamed bodies formed by in-mold foaming of thermoplastic resins (such as polypropylene resins) are widely used for various applications, such as automotive interior materials and cushioning materials. Previously, automotive interior materials used materials with flame retardancy meeting the FMVSS302 standard. However, with the recent shift towards electric vehicles, components related to electrical devices such as lithium-ion battery packs are increasingly required to have higher flame retardancy. For example, Patent Document 1 discloses a technique that obtains polyolefin pre-foamed particles that provide excellent flame retardancy by adding a specific amount of organophosphorus compound and hindered amine to polyolefin resin foamed particles.

[0003] Existing technical documents

[0004] Patent documents

[0005] Patent Document 1: International Publication No. 2016 / 052739 Summary of the Invention

[0006] The problem the invention aims to solve

[0007] However, the existing technologies described above are not entirely effective from a flame-retardant point of view, and there is room for further improvement.

[0008] In view of the above situation, an objective of one embodiment of the present invention is to provide polypropylene foamed granules that can provide polypropylene foamed molded articles with superior flame retardancy compared with the prior art.

[0009] Solution for solving the problem

[0010] The inventors conducted in-depth research to solve the above-mentioned problems, and as a result, completed this invention.

[0011] That is, one embodiment of the present invention includes the following configuration.

[0012] A polypropylene-based foamed granule comprises a polypropylene resin (A), an organophosphorus compound (B), and a hindered amine (C), comprising more than 10.0% and less than 20.0% by weight of the organophosphorus compound (B) and 1.0% to 10.0% by weight of the hindered amine (C) relative to 100% by weight of the total amount of the aforementioned polypropylene-based foamed granule.

[0013] A method for manufacturing polypropylene foamed granules includes the following steps: a dispersion step in which polypropylene resin granules, an aqueous dispersion medium, and a foaming agent are dispersed in a container; and a release step in which the dispersion obtained by the aforementioned dispersion step is released into a region with a pressure lower than that inside the aforementioned container, wherein the aforementioned polypropylene resin granules contain more than 10.0% by weight and less than 20.0% by weight of an organophosphorus compound (B) and 1.0% to 10.0% by weight of hindered amine (C) relative to 100% by weight of the total amount of the aforementioned polypropylene resin granules.

[0014] The effects of the invention

[0015] According to one embodiment of the present invention, the following effect is achieved: compared with the prior art, polypropylene foamed granules that can provide polypropylene foamed molded articles with better flame retardancy can be provided. Detailed Implementation

[0016] The following description describes one embodiment of the present invention, but the present invention is not limited thereto. The present invention is not limited to the configurations described below, and various modifications can be made within the scope shown in the claims. Furthermore, embodiments or examples obtained by combining the technical means disclosed in different embodiments or examples are also included within the technical scope of the present invention. Moreover, by combining the technical means disclosed in each embodiment, new technical features can be formed. It should be noted that all academic and patent documents described in this specification are incorporated herein by reference. Additionally, in this specification, unless otherwise specified, "A~B" representing a numerical range means "A or more (including A and greater than A) and B or less (including B and less than B)".

[0017] In addition, unless otherwise specified, this specification will also include information from X. 1 The structural unit of a single entity, originating from X 2 The structural unit of a single entity… and X n A copolymer in which monomers (n is an integer greater than or equal to 2) serve as structural units is called "X". 1 / X 2 / … / X n "Copolymer". As X 1 / X 2 / … / X n Copolymers, unless otherwise specified, are not particularly limited in terms of polymerization method and can be random copolymers, alternating copolymers, block copolymers, or graft copolymers.

[0018] In addition, in this specification, structural units derived from monomer X contained in polymers or copolymers are sometimes referred to as "unit X".

[0019] [1. Technical concept of the present invention]

[0020] The technology described in Patent Document 1 was excellent given the level of technology at the time of the patent application. However, in recent years, there has been a trend in various industrial sectors (such as electrical and electronic equipment, especially equipment used in electric vehicles, etc.) to have more stringent flame retardancy standards compared to those at the time of the patent application, requiring polypropylene foam molded articles with superior flame retardancy.

[0021] Going forward, as more stringent flame retardancy standards emerge, it is predicted that polypropylene-based foamed molded bodies will be required to meet standards such as the Oxygen Index (OI) and the Vertical Burning Test (UL94). In fact, fire safety regulations classify substances with an OI of 26% or lower as designated combustibles. Here, OI, according to JIS K7201, represents the minimum oxygen concentration (volume %) required for sustained combustion of a material. In other words, foamed molded bodies that meet the OI standard (e.g., OI of 26% or higher) are considered to have excellent non-flammability. Furthermore, UL94 is a standard for the duration of combustion of a material and for ensuring that even if burning particles fall (dripping) during combustion, surrounding combustibles do not ignite (the falling particles extinguish themselves before contacting surrounding combustibles; this can also be referred to as whether ignition is caused by dripping). In other words, foamed molded bodies that meet the UL94 standard (especially standard V-0) are considered to have excellent self-extinguishing properties.

[0022] The technique of imparting flame retardancy to polypropylene foamed moldings by adding halogenated compounds is known. However, in recent years, the harmful effects of halogenated compounds, especially bromine-containing organic compounds (such as polybrominated diphenyl ethers), on the environment and human health have been discovered, and they are increasingly being regarded as a problem. For example, since July 2006, EU regulations have prohibited the manufacture and use of pentabromodiphenyl ether and octabromodiphenyl oxide, and the use of decabromodiphenyl ether is restricted.

[0023] Under these circumstances, it is desirable to have polypropylene foamed molded articles that do not contain halogenated compounds and have superior flame retardancy compared to conventional foamed molded articles (such as those described in Patent Document 1).

[0024] Under the aforementioned circumstances, the inventors conducted in-depth research in order to provide polypropylene foamed granules capable of providing polypropylene foamed molded articles with superior flame retardancy, and as a result discovered the following insights, thereby completing the present invention: According to the following polypropylene foamed granules, it is possible to provide polypropylene foamed molded articles with superior flame retardancy, wherein the polypropylene foamed granules comprise a polypropylene resin (A), an organophosphorus compound (B), and a hindered amine (C), and contain more than 10.0% and less than 20.0% by weight of cyclic phosphonate (B) and 1.0% to 10.0% by weight of hindered amine (C) relative to 100% by weight of the total amount of the aforementioned polypropylene foamed granules.

[0025] [2. Polypropylene foamed granules]

[0026] The polypropylene foamed particles of one embodiment of the present invention comprise a polypropylene resin (A), an organophosphorus compound (B), and a hindered amine (C), comprising more than 10.0% and less than 20.0% by weight of the organophosphorus compound (B) and 1.0% to 10.0% by weight of the hindered amine (C) relative to 100% by weight of the total amount of the aforementioned polypropylene foamed particles.

[0027] By molding the polypropylene foamed granules according to one embodiment of the present invention using a known method, a polypropylene foamed molded article can be provided.

[0028] In this specification, "polypropylene foamed granules" is sometimes referred to as "foamed granules", "polypropylene foamed granules according to one embodiment of the present invention" is sometimes referred to as "the foamed granules", and "polypropylene resin foamed molded body" is sometimes referred to as "foamed molded body".

[0029] This foamed granule has the aforementioned composition, and therefore has the advantage of providing foamed molded articles with excellent flame retardancy. In other words, this foamed granule can provide polypropylene-based foamed molded articles with excellent self-extinguishing and / or non-flammable properties.

[0030] <Polypropylene Resin (A)>

[0031] In this specification, polypropylene resin (A) refers to a resin in which at least 50 mol% of 100 mol% of all structural units contained in the resin are derived from propylene monomers. In this specification, "structural units derived from propylene monomers" are sometimes referred to as "propylene units".

[0032] The polypropylene resin (A) can be (a) a homopolymer of propylene, (b) a block copolymer, alternating copolymer, random copolymer, or graft copolymer of propylene and monomers other than propylene, or (c) a mixture of two or more of these. Among these, the polypropylene resin (A) is preferably a random copolymer of propylene and monomers other than propylene, which has the advantage of being able to process the resin particles and foam particles at low heating temperatures in the foaming and in-mold molding processes described later. Alternatively, "a random copolymer of propylene and monomers other than propylene" can be described as a random copolymer comprising structural units derived from propylene and structural units derived from monomers other than propylene.

[0033] Polypropylene resin (A) may have one or more structural units derived from monomers other than propylene monomers in addition to propylene units, and may have more than one type of such unit. Sometimes, the monomers other than propylene monomers used in the manufacture of polypropylene resin (A) are also referred to as "comonomers". Sometimes, the structural units derived from monomers other than propylene monomers contained in polypropylene resin are also referred to as "comonomer units".

[0034] Examples of comonomers include α-olefins with 2 or 4 to 12 carbon atoms, such as ethylene, 1-butene, isobutene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 3,4-dimethyl-1-butene, 1-heptene, 3-methyl-1-hexene, 1-octene, and 1-decene.

[0035] Specific examples of polypropylene-based resins (A) include polypropylene homopolymers, ethylene / propylene random copolymers, 1-butene / propylene random copolymers, 1-butene / ethylene / propylene random copolymers, ethylene / propylene block copolymers, 1-butene / propylene block copolymers, propylene / vinyl chloride copolymers, propylene / maleic anhydride copolymers, and styrene-modified polypropylene-based resins. One of these polypropylene-based resins (A) can be used alone, or two or more can be used in combination. Among these, ethylene / propylene random copolymers and 1-butene / ethylene / propylene random copolymers are suitable from the viewpoints of good foaming properties of the resulting foamed particles and good moldability of the molded body. It should be noted that the terms 1-butene and butene-1 are synonymous.

[0036] As a polypropylene resin (A), the case of using an ethylene / propylene random copolymer (denoted as Case A) is considered. In Case A, the ethylene content in the ethylene / propylene random copolymer is preferably 0.2 wt% to 15.0 wt% per 100 wt% of each copolymer, more preferably 0.5 wt% to 10.0 wt%, and even more preferably 0.5 wt% to 4.0 wt%. It can also be said that the ethylene content refers to the content of structural units (ethylene units) derived from ethylene. When the ethylene unit content in the ethylene / propylene random copolymer is (i) 0.2 wt% or more, there is a tendency for the foaming properties of the foamed particles and / or the moldability of the resulting foamed particles to become better when manufacturing the foamed particles, and (ii) 15.0 wt% or less, there is no concern about a decrease in the mechanical properties of the foamed molded articles obtained from the foamed particles.

[0037] As for the polypropylene resin (A), the case of using a 1-butene / ethylene / propylene random copolymer (denoted as Case B) is considered. The ethylene content in the 1-butene / ethylene / propylene random copolymer is preferably 0.1% to 10.0% by weight per 100% of each copolymer, more preferably 0.2% to 5.0% by weight, and even more preferably 0.5% to 1.0% by weight. When the ethylene unit content in the 1-butene / ethylene / propylene random copolymer is (i) 0.1% by weight or more, there is a tendency for the foaming properties of the foamed particles and / or the moldability of the resulting foamed particles to become better when manufacturing the foamed particles, and (ii) 10.0% by weight or less, there is no concern about a decrease in the mechanical properties of the foamed molded articles obtained from the foamed particles.

[0038] Furthermore, in case B, the 1-butene content in the 1-butene / ethylene / propylene random copolymer is preferably 0.2 wt% to 15.0 wt% in 100 wt% of the copolymer, more preferably 1.0 wt% to 10.0 wt%, and even more preferably 2.0 wt% to 7.0 wt%. It can also be said that the 1-butene content refers to the content of structural units derived from 1-butene (1-butene units). When the 1-butene unit content in the 1-butene / ethylene / propylene random copolymer is (i) 0.2 wt% or more, there is a tendency for the foaming properties of the foamed particles and / or the moldability of the resulting foamed particles to improve during manufacturing; when it is (ii) 15.0 wt% or less, there is no concern about a decrease in the mechanical properties of the foamed molded articles obtained from the foamed particles.

[0039] Furthermore, in case B, the total content of ethylene units and 1-butene units in the 1-butene / ethylene / propylene random copolymer is preferably 0.5% to 15.0% by weight, more preferably 0.5% to 10.0% by weight, and even more preferably 2.0% to 6.0% by weight, in 100% by weight of the 1-butene / ethylene / propylene random copolymer. When the total content of ethylene units and 1-butene units in the 1-butene / ethylene / propylene random copolymer is (i) 0.5% by weight or more, there is a tendency for the foaming properties of the foamed particles and / or the formability of the resulting foamed particles to become better when manufacturing the foamed particles, and (ii) when it is 10.0% by weight or less, there is no concern about a decrease in the mechanical properties of the foamed molded articles obtained from the foamed particles.

[0040] The content of propylene units in the polypropylene resin (A) is 50 mol% or more, preferably 75 mol% or more, more preferably 90 mol% or more, and even more preferably 95 mol% or more, out of 100 mol% of all structural units contained in the polypropylene resin (A). By keeping the content of propylene units in the polypropylene resin (A) within the above range, the resulting foamed molded body has the advantage of good heat resistance, mechanical strength, and impact resistance. Furthermore, the upper limit of the content of propylene units in the polypropylene resin (A) is not particularly limited; for example, it can be 97 mol% or less, or it can be 100 mol%.

[0041] The melting point of the polypropylene resin (A) is preferably 125.0°C to 160.0°C, more preferably 130.0°C to 158.0°C, even more preferably 135.0°C to 152.0°C, even more preferably 138.0°C to 149.0°C, further preferably 139.0°C to 146.0°C, and particularly preferably 141.0°C to 145.0°C. When the melting point of the polypropylene resin (A) is (i) 125.0°C or higher, a foamed molded body with excellent dimensional stability at high temperatures can be obtained; when it is (ii) 160.0°C or lower, a foamed molded body can be formed by in-mold foaming under low steam pressure.

[0042] In this specification, the melting point of the polypropylene resin is determined by differential scanning calorimetry (hereinafter referred to as "DSC method"). The specific operating steps are as follows: (1) The polypropylene resin is melted by heating 5 mg to 6 mg of the resin from 40.0 °C to 220.0 °C at a heating rate of 10.0 °C / min; (2) The melted polypropylene resin is then crystallized by cooling the temperature of the melted resin from 220.0 °C to 40.0 °C at a cooling rate of 10.0 °C / min; (3) The crystallized polypropylene resin is then further heated from 40.0 °C to 220.0 °C at a heating rate of 10 °C / min. The temperature of the peak (melting peak) of the DSC curve of the polypropylene resin obtained at the second heating (i.e., at (3)) can be used as the melting point of the polypropylene resin. It should be noted that when multiple peaks (melting peaks) appear in the DSC curve of the polypropylene resin obtained during the second heating using the above method, the temperature of the peak with the largest heat of fusion (melting peak) is taken as the melting point of the polypropylene resin. As a differential scanning calorimeter, a model such as the DSC6200 manufactured by Seiko Instruments Inc. can be used.

[0043] The melt index (MI) of the polypropylene resin (A) is not particularly limited, but is preferably 3.00 g / 10 min to 30.00 g / 10 min, more preferably 4.00 g / 10 min to 20.00 g / 10 min, even more preferably 5.00 g / 10 min to 15.00 g / 10 min, and particularly preferably 6.00 g / 10 min to 13.00 g / 10 min. It should be noted that MI is sometimes also referred to as "melt flow rate (MFR)".

[0044] When the MI of the polypropylene resin is 3.00 g / 10 min or higher, the polypropylene resin exhibits good flowability during foaming and is easy to foam. Furthermore, when the MI of the polypropylene resin is 30.00 g / 10 min or lower, the polypropylene resin possesses moderate flowability, thus enabling the production of foamed granules with a high expansion ratio. In particular, if the MI of the polypropylene resin (A) is between 3.00 g / 10 min and 8.00 g / 10 min, it is possible to efficiently manufacture foamed granules that can appropriately provide a high density (e.g., a density exceeding 92.0 g / L) in the foamed molded body.

[0045] In this specification, the MI value of the polypropylene resin is the value measured using the MI measuring instrument described in JIS K7210:1999 under the following conditions: orifice diameter of 2.0959±0.005 mmφ, orifice length of 8.000±0.025 mm, load of 2.16 kgf, and temperature of 230℃ (230±0.2℃). It should be noted that when the polypropylene resin (A) is a mixture of multiple copolymers, the MI of the polypropylene resin (A) refers to the melting point of that mixture.

[0046] In this foamed granule, relative to 100% by weight of the total amount of polypropylene-based foamed granules, it is preferable to contain 70.0% by weight or more and less than 89.0% by weight of polypropylene-based resin (A), more preferably 75% to 85% by weight, and even more preferably 77% to 87% by weight. When the foamed granules contain (i) more than 70.0% by weight of polypropylene-based resin (A), a foamed molded body with excellent strength (e.g., compressive strength) without breakage can be obtained, and when it contains (ii) less than 89.0% by weight, a foamed molded body with excellent flame retardancy can be stably obtained.

[0047] Polypropylene resin (A) can be obtained using known methods. There are no particular limitations on the polymerization catalyst used in the synthesis of polypropylene resin (A), and Ziegler catalysts and metallocene catalysts, etc., can be used.

[0048] <Organophosphorus compounds (B)>

[0049] This foamed granule contains, relative to 100% by weight of the total amount of polypropylene foamed granules, more than 10.0% by weight and less than 20.0% by weight of an organophosphorus compound (B). This foamed granule, by having the above-described structure, has the advantage of providing foamed granules capable of providing foamed molded articles with excellent flame retardancy.

[0050] In this foamed granule, relative to 100% by weight of the total amount of polypropylene foamed granules, it contains more than 10.0% by weight and less than 20.0% by weight of an organophosphorus compound (B), preferably 12.0% to 19.0% by weight, more preferably 13.0% to 18.0% by weight. When the foamed granules contain (i) more than 10.0% by weight of an organophosphorus compound (B), a foamed molded body with excellent flame retardancy can be stably obtained, and when it contains (ii) less than 20.0% by weight, a foamed molded body with excellent strength (e.g., compressive strength) and no breakage can be obtained.

[0051] As for organophosphorus compounds (B), there are no particular limitations on any organophosphorus compound other than phosphate esters, phosphates, and triarylphosphine oxides. Various other organophosphorus compounds (subclasses of organophosphorus compounds) known to those skilled in the art may be used. These organophosphorus compounds (B) may be used alone or in combination of two or more.

[0052] As an embodiment of the present invention, the organophosphorus compound (B) specifically includes phosphonates; organophosphites; organophosphinates; metal salts of phosphinates or secondary phosphonates; phosphites; polyol phosphate esters; and other nitrogen-containing organophosphorus compounds. Among these, phosphonates are preferred as organophosphorus compounds (B) from the perspective of providing foamed molded articles with superior non-flammability and / or self-extinguishing properties. It should be noted that, among the above-mentioned organophosphorus compounds, compounds other than other nitrogen-containing organophosphorus compounds are preferably nitrogen-free. That is, organophosphorus compounds (B) other than nitrogen-containing organophosphorus compounds are preferably nitrogen-free.

[0053] (phosphonates)

[0054] Phosphonates refer to esters containing R-PO(OH)2 groups and / or R-PO(OR) groups. 1 )2-yl (here, R is a hydrocarbon group such as methyl, benzyl, aryl, alkynyl, propadienyl, vinyl or substituted vinyl, etc., R 1 Esters and metaesters (containing hydrocarbon groups such as alkyl or aryl groups), and their salts.

[0055] As phosphonates, more specifically, examples include alkylphosphonic acids, arylphosphonic acids, and their esters; monophosphonates; cyclic bisphosphonates; and cyclic phosphonates. Among these, cyclic phosphonates are preferred, and among cyclic phosphonates, cyclic bisphosphonates are particularly preferred. Therefore, the organophosphorus compound (B) according to one embodiment of the present invention is preferably at least one nitrogen-free organophosphorus compound selected from the group consisting of (i) alkylphosphonic acids, arylphosphonic acids and their esters, and (ii) cyclic phosphonates, more preferably a cyclic phosphonate, and among cyclic phosphonates, cyclic bisphosphonates are particularly preferred.

[0056] Examples of cyclic phosphonates include organophosphorus compounds with the following structural formula (i):

[0057]

[0058] In the above structural formula (i), R 1 and R 2 Independently for C 1-4 Alkyl, R 3For H or C 1-4 Alkyl, R 4 C 9-22 Alkyl, C 9-22 cycloalkyl, C 9-22 Aryl or C 9-22 Aryl alkyl group, and n = 0 or 1.

[0059] More specifically, the cyclic phosphonate ester represented by the above structural formula (i) is described in detail in French Patent Application Publication No. 1503429.

[0060] As cyclic phosphonates, organophosphorus compounds represented by the following structural formula (ii), such as pentaerythritol diphosphonate, can also be suitably used:

[0061]

[0062] In the above structural formula (ii), A 1 and A 2 Independently for C 1-10 Alkyl, C 2-10 Alkenyl, benzyl, phenylethyl, phenyl or naphthyl.

[0063] That is, cyclic bisphosphonates are particularly preferred to be pentaerythritol bisphosphonates.

[0064] More specifically, cyclic bisphosphonates have been disclosed in U.S. Patent No. 4,174,343 and UK Patent Application Publication No. 1,515,223.

[0065] Among cyclic bisphosphonates, especially from the perspective of obtaining foamed molded articles with excellent heat resistance and dimensional stability, pentaerythritol bisphosphonate (AFLAMMIT (registered trademark) PCO900 (phosphorus content of 24%)) shown in the following structural formula (iii) is particularly preferred.

[0066]

[0067] Alternatively, as other cyclic phosphates, compounds disclosed in French Patent Application Publication No. 1503429 may be used.

[0068] (Organic phosphites)

[0069] Examples of organic phosphites include, for instance, dimethyl phosphite, diethyl phosphite, trimethyl phosphite, dibutyl phosphite, triisopropyl phosphite, dibenzyl phosphite, bis(2,2,2-trifluoroethyl) phosphite, tri(2,2,2-trifluoroethyl) phosphite, tri(1,1,1,3,3,3-hexafluoro-2-propyl) phosphite, and diphenyl phosphite, as well as alkyl phosphite and aryl alkyl phosphite (here, the alkyl group preferably has 1 to 4 carbon atoms); trimethylolethane cyclic phosphites (as 4-methyl-2,6,7-trioxa-1-phosphabicyclo[2.2.2]octane are also known). Cyclic phosphites such as 2-hydroxy-4,5-dimethyl-1,3,2-dioxaphosphane (2,3-butylene hydrogen phosphite), 2-hydroxy-4-methyl-1,3,2-dioxaphosphane, 2-hydroxy-4-methyl-1,3,2-dioxaphosphane (propylene hydrogen phosphite), 2-hydroxy-1,3,2-dioxaphosphane (trimethylene hydrogen phosphite), 2-hydroxy-5,5-dimethyl-1,3,2-dioxaphosphane, and 2-hydroxy-4-propyl-5-ethyl-1,3,2-dioxaphosphane, etc., as outlined in U.S. Patent No. 3,152,164.

[0070] (Organic hypophosphite and metal salts of hypophosphite or secondary phosphite)

[0071] Phosphinoic acid or its metal salts refer to those with the chemical formulas RR'P(=O)-OMe and MeO-PR(=O)-R. 1 -PR'(=O)-Ome represents the metal salt of a compound (phosphonic acid or diphosphonic acid). Here, R and R' are independently chosen from C. 1-6 Alkyl, C 3-8 cycloalkyl, C 6-16 The group consisting of aryl or arylalkyl groups, where Me is a metal derived from Group I (bases), Group II (alkaline earths or zinc), or Group III (e.g., aluminum) of the periodic table, and R 1 C 1-6 Alkylene, arylene, arylalkylene, or aromatic-dialkylene linkage groups.

[0072] Metal salts of organosphinic acid salts, phosphinic acids, or diphosphinic acids, and more specifically, alkali, magnesium, zinc, and aluminum salts of dimethylphosphinic acid, methylethylphosphinic acid, methylpropylphosphinic acid, methylhexylphosphinic acid, ethylphenylphosphinic acid, diethylphosphinic acid, ethane-1,2-dimethylphosphinic acid, ethane-1,2-diethylphosphinic acid, ethane-1,2-diphenylphosphinic acid, and butane-1,4-dimethylphosphinic acid, are listed without particular limitation.

[0073] (phosphonites)

[0074] Examples of phosphonites include aluminum diethylphosphonite.

[0075] (Polyol Phosphate Alcohol)

[0076] As polyol phosphate ester alcohols, commercially available compounds such as bis(pentaerythritol phosphate ester alcohol) alkyl phosphonates (here, the alkyl group has 1 to 4 carbon atoms) or (pentaerythritol phosphate ester alcohol) phosphites can be listed.

[0077] (Other nitrogen-containing organophosphorus compounds)

[0078] As organophosphorus compounds (B), nitrogen-containing organophosphorus compounds can be used. Nitrogen-containing organophosphorus compounds are those that contain at least one nitrogen atom in their structural formula. Examples of nitrogen-containing organophosphorus compounds include, for example, aminophosphates, organophosphazenes (and their salts), phosphorous amides, phosphoramides, and phosphonamides.

[0079] As an aminophosphate ester, a compound represented by the following structural formula (iv) is preferred:

[0080]

[0081]

[0082] In the above structural formula (iv), R is CH3 or CH2CH3, and n1 is 2 to 10. The compound shown in the above structural formula (iv) is described in detail in International Publication No. 2009 / 153034.

[0083] Organophosphazenes (also known as iminophosphine or phosphonoimides) and their salts (specifically, chlorides and fluorides) refer to compounds containing a phosphorus atom covalently bonded to a nitrogen atom via a double bond and covalently bonded to three other atoms or free radicals via single bonds. Examples include bis(triphenylphosphine) chloride imine, BEMP (2-tert-butylimino-2-diethylamino-1,3-dimethylperhydro-1,3,2-diazaphosphazene), BTPP ((tert-butylimino)tri-(pyrrolidine)phosphine), and t-Bu-P4 (3-tert-butylimino-1,1,1,5,5,5-hexa(dimethylamino)-3{[tris(dimethylamino)phosphine]amino}-1λ). 5 ,3λ 5 ,5λ 5 -1,4-triphosphadiene). Preferably, it is a cyclic organophosphazene represented by the following structural formula (v):

[0084]

[0085] Here, in the above structural formula (v), m is 3 to 20, and each Q group is one or more selected from the group consisting of phosphate ester groups, aryloxy groups or alkoxy groups that do not contain phosphorus atoms and halogen atoms.

[0086] The compound represented by the above structural formula (v) is described in detail in International Publication No. 2009 / 055993.

[0087] As a cyclic organophosphorus nitrile, specifically, the compound DPPPZ, represented by the following structural formula (vi) (where Ph represents phenyl), can be listed:

[0088]

[0089] (Hindered amine (C))

[0090] This foamed granule contains 1.0% to 10.0% by weight of hindered amine (C) relative to 100% by weight of the total amount of polypropylene foamed granules. By having the above-described structure, this foamed granule has the following advantages: it provides foamed granules capable of providing foamed molded articles with excellent flame retardancy.

[0091] In this foamed granule, relative to 100% by weight of the total amount of polypropylene foamed granules, it contains 1.0% to 10.0% by weight of hindered amine (C), preferably 2.0% to 8.0% by weight, more preferably 2.5% to 7.0% by weight, and even more preferably 3.0% to 6.0% by weight. When this foamed granule contains (i) more than 0.1% by weight of hindered amine (C), a foamed molded body with excellent non-flammability and self-extinguishing properties can be obtained. When it contains (ii) less than 10.0% by weight, the adhesion (agglomeration) of resin particles to each other can be suppressed in the foaming process described later.

[0092] In this specification, a hindered amine (C) refers to a hindered amine having an OR group (here, R is a saturated or unsaturated hydrocarbon group) directly substituted on the N atom (hereinafter sometimes referred to as an N-substituted hindered amine). In other words, in this specification, hindered amines that do not have an OR group directly substituted on the N atom are not considered hindered amines (C). As a hindered amine (C), there is no particular limitation as long as it has an OR group (here, R is a saturated or unsaturated hydrocarbon group) directly substituted on the N atom, and various known subclasses of hindered amines can be used. As a hindered amine (C), one hindered amine can be used alone, or two or more hindered amines can be used in combination.

[0093] In one embodiment of the present invention, the hindered amine (C) is preferably an N-substituted hindered amine containing a triazine component. There is no particular limitation on the N-substituted hindered amine containing a triazine component (hereinafter sometimes referred to as a hindered amine containing a triazine skeleton), but preferably is (i) the compound with CAS number 191680-81-6 ((i-1) the product of reacting an oxidized N-butyl-2,2,6,6,-tetramethyl-4-piperidinamine with 2,4,6-trichloro-1,3,5-triazine with cyclohexane, and the product of reacting with N,N'-bis(3-aminopropyl)ethylenediamine, also referred to as (i-2) 2,4-bis((1-cyclohexyloxy-2,2,6,6-tetramethylpiperidin-4-yl)butylamino)-6-chloro-metatrimethylamine). The reaction product of azines with N,N'-bis(3-aminopropyl)ethylenediamine is also known as (i-3)N,N',N”'-tri{2,4-bis[(1-hydroxy-2,2,6,6-tetramethylpiperidin-4-yl)alkylamino]-s-triazin-6-yl}-3,3'-ethylenediiminodipropylamine); or (ii) bis(1-undecyloxy-2,2,6,6-tetramethylpiperidin-4-yl) carbonate. Alternatively, isomers or cross-linked derivatives of these compounds may also be used. As hindered amines containing a triazine skeleton, they are described in detail on page 2, line 32 to page 4, line 6 of the specification of European Patent No. 0889085.

[0094] Commercially available products can also be used as hindered amines containing a triazine skeleton. Examples of commercially available hindered amines containing a triazine skeleton include BASF's FLAMSTAB (registered trademark) NOR116 (CAS number 191680-81-6), CLARIANT's HOSTAVIN (registered trademark) NOW XP, and ADEKA's ADEKASTABLA-81 (bis(1-undecyloxy-2,2,6,6-tetramethylpiperidin-4-yl) carbonate).

[0095] In one embodiment of the present invention, the hindered amine (C) can be a compound represented by the following structural formula (vii):

[0096]

[0097] In the above structural formula (vii), G 1 and G 2 Independently for C 1-8 Alkyl or pentamethylene; Z 1 and Z 2 They are methyl, or Z, respectively. 1 and Z 2Together they form a bonded component, which may be optionally additionally substituted with an ester group, ether group, amide group, amino group, carboxyl group, or urethane group; and E is C. 1-8 Alkoxy, C 5-12 Cycloalkoxy, C 7-15 Arylalkoxy, -OC(O)-C 1-18 Alkyl or -OT-(OH) b Base; here, T is C 1-18 alkylene chain, C 5-18 Cycloalkyl chain or C 5-18 Cycloalkylene chains, phenyl groups, or C-terminated chains 1-4 Alkyl-substituted phenyl-substituted C 1-4 Alkylene chain; b is 1 to 3, and is less than the number of carbon atoms in T. In addition, when b is 2 or 3, each hydroxyl group is attached to a different carbon atom in T.

[0098] The compound shown in the above structural formula (vii) is described in detail in the specification of European Patent No. 2225318, and more specifically, it is illustrated on page 5, line 35 to page 25, line 48 of the specification of European Patent No. 2225318.

[0099] In one embodiment of the present invention, the hindered amine (C) may be a compound represented by the following structural formula (viii):

[0100]

[0101] In the above structural formula (viii), R is hydrogen or methyl, and R 1 Choose C freely 1-18 Alkyl, C 2-18 alkenyl, C 2-18 alkynyl group, C 5-12 cycloalkyl, C 5-8 Cycloalkenyl, C 6-10 Aryl and C 7-9 Groups in the group consisting of aralkyl groups.

[0102] More specifically, the compounds shown in the above structural formula (viii) are illustrated in European Patent No. 0309402, page 3, line 33 to page 8, line 58.

[0103] In one embodiment of the present invention, the hindered amine (C) can be a compound represented by the following structural formula (ix):

[0104]

[0105] In the above structural formula (ix), E, ​​k, Y, W, R1 to R7 and G1 to G4 are as specified in the specification of U.S. Patent No. 8,598,369.

[0106] More specifically, the compounds represented by the above structural formula (ix) are illustrated in Examples 1-12 and Tables 1-5 of U.S. Patent No. 8,598,369.

[0107] <Ratio of components in foamed granules>

[0108] (Ratio of hindered amine (C) to organophosphorus compound (B))

[0109] In this specification, the ratio of hindered amine (C) to organophosphorus compound (B) (hereinafter referred to as the ratio (B) / (C)) refers to the ratio of the weight of hindered amine (C) contained in the foamed granule to the weight of organophosphorus compound (B) contained in the foamed granule. In this foamed granule, the ratio (B) / (C) is not particularly limited.

[0110] In one embodiment of the present invention, the ratio (B) / (C) varies depending on the type of organophosphorus compound (B) and hindered amine (C) contained in the foamed particles, and therefore cannot be generalized. A ratio of 1.0 to 20.0 is preferred, more preferably 2.0 to 10.0, and even more preferably 3.0 to 5.0. When the ratio (B) / (C) is 1.0 to 20.0, the resulting foamed molded body exhibits excellent flame retardancy and can suppress the ignition of surrounding combustibles caused by the generation of burning particles during combustion (i.e., excellent self-extinguishing properties), without concern about damage to the various physical properties (mechanical properties, cushioning, etc.) of the foamed molded body.

[0111] (The ratio of the total amount of organophosphorus compounds (B) to hindered amines (C) relative to polypropylene resin (A))

[0112] In this specification, the ratio of the total amount of organophosphorus compound (B) to hindered amine (C) relative to polypropylene resin (A) (hereinafter referred to as ratio (A) / {(B)+(C)}) means the ratio of the weight of polypropylene resin (A) contained in the foamed granules to the total weight of organophosphorus compound (B) and hindered amine (C) contained in the foamed granules. In this foamed granule, ratio (A) / {(B)+(C)} is not particularly limited.

[0113] In one embodiment of the present invention, the ratio (A) / {(B)+(C)} is preferably 1 to 10, more preferably 1 to 7, and even more preferably 1 to 5. When the ratio (A) / {(B)+(C)} in the foamed particles is (i) 10 or less, the flame retardancy of the resulting foamed molded article becomes better. In addition, when it is (ii) 1 or more, the surface aesthetics of the resulting foamed molded article become better.

[0114] (Other additives)

[0115] In addition to organophosphorus compounds and hindered amines, the foamed granules may optionally contain other additives within a range that does not impair the effects of the present invention. Examples of other additives include antioxidants, UV light absorbers, peroxide scavengers, inorganic nucleating agents, organic nucleating agents, water-absorbing substances, antistatic agents, antioxidants, light stabilizers, crystallizing nucleating agents, conductive agents, lubricants, fillers, carbon black, and powdered activated carbon. In the manufacture of these foamed granules, these other additives can be added directly to the blends or polypropylene resin compositions described later during the manufacture of the resin granules, or they can be pre-prepared as a masterbatch by containing the additive at a high concentration in other resins, and then added to the aforementioned blends or polypropylene resin compositions. Polypropylene resins are preferred as the resin used in the preparation of the masterbatch resin.

[0116] Examples of antioxidants include alkylated monophenols, alkylthiomethylphenols, hydroquinones and alkylated hydroquinones, tocopherols, diphenyl thiohydroxy ethers, alkylidene bisphenols, benzyl compounds containing oxygen, benzyl compounds containing nitrogen, benzyl compounds containing sulfur, hydroxybenzyl malonate, aromatic hydroxybenzyl compounds, acylaminophenols, and amides and esters of hydroxyphenylpropionic acid. These antioxidants can be used alone or in combination of two or more.

[0117] Regarding the content of antioxidants in the foamed granules, from the viewpoint of being able to suppress the deterioration of the resulting foamed molded body at high temperatures (e.g., around 110°C) and thus maintain flame retardancy for a longer period of time, it is preferably 0.03% to 1.00% by weight, more preferably 0.05% to 0.70% by weight, and even more preferably 0.10% to 0.50% by weight, relative to 100% by weight of the total amount of polypropylene foamed granules.

[0118] Examples of UV light absorbers include benzotriazole, benzophenone, benzoic acid esters, nickel complexes, hindered amines (excluding hindered amines (C) of this invention) that do not have an OR group directly bonded to the N atom, and oxalamide. These UV light absorbers can be used alone or in combination of two or more.

[0119] Regarding the content of UV absorber in the foamed granules, from the viewpoint of being able to suppress the degradation of the obtained foamed molded body caused by ultraviolet light and thus maintain flame retardancy for a longer period of time, it is preferably 0.01% to 1.00% by weight, more preferably 0.05% to 0.50% by weight, and even more preferably 0.10% to 0.30% by weight, relative to 100% by weight of the total amount of polypropylene foamed granules.

[0120] Examples of inorganic nucleating agents include talc, titanium dioxide, silica, silicates, alumina, diatomaceous earth, calcium carbonate, magnesium oxide, magnesium carbonate, magnesium sulfate, calcium phosphate, feldspar apatite, and barium sulfate. Examples of silicates include talc, magnesium silicate, kaolin, hydrous kaolin, dickite, aluminum silicate, and zeolite. These inorganic nucleating agents can be used individually or in combination of two or more.

[0121] Regarding the content of the inorganic nucleating agent in the foamed granules, from the viewpoint of uniformity of average bubble diameter, it is preferably 0.005% to 3.000% by weight, more preferably 0.010% to 2.000% by weight, further preferably 0.030% to 1.000% by weight, and particularly preferably 0.030% to 0.500% by weight, relative to 100% of the total amount of polypropylene foamed granules. In particular, by setting the content of the inorganic nucleating agent in the foamed granules to 0.030% to 0.500% by weight, a foamed molded article with uniform average bubble diameter and superior flame retardancy can be provided.

[0122] Examples of organic nucleating agents include monocarboxylic acids or polycarboxylic acids (such as adipic acid or diphenylacetic acid) and their salts, ionic copolymers, etc. These organic nucleating agents can be used alone or in combination of two or more.

[0123] Regarding the content of the organic nucleating agent in the foamed granules, from the viewpoint of uniformity of average bubble diameter, it is preferably 0.005% to 2.000% by weight, more preferably 0.010% to 1.000% by weight, and most preferably 0.030% to 0.500% by weight, relative to 100% of the total amount of polypropylene foamed granules.

[0124] Examples of absorbent substances include glycerol, diglycerol, polyethylene glycol, C12-C18 fatty alcohols (such as pentaerythritol, cetyl alcohol, stearyl alcohol), melamine, isocyanuric acid, melamine-isocyanuric acid condensate, and zinc borate. These absorbent substances can be used alone or in combination of two or more.

[0125] Among these, glycerol and polyethylene glycol are preferred from the perspective of not worrying about promoting the miniaturization of the average bubble diameter of the foamed particles and having good affinity with polypropylene resin (A).

[0126] Regarding the content of the water-absorbing substance in these foamed granules, from the perspective of effectively obtaining foamed granules with low density (e.g., 40.0 g / L or less), it is preferably 0.01 wt% to 1.00 wt% relative to 100 wt% of the total amount of polypropylene foamed granules, more preferably 0.05 wt% to 0.70 wt%, and even more preferably 0.10 wt% to 0.60 wt%. When the content of the water-absorbing substance is (i) 0.01 wt% or more, the effect of imparting foaming properties through the water-absorbing substance can be sufficiently obtained, and when it is (ii) 1.00 wt% or less, there is no concern about excessive shrinkage of the foamed granules. It should be noted that when producing foamed granules with a high density (e.g., density exceeding 40.0 g / L but less than 400.0 g / L), foamed granules can be effectively obtained even without adding water-absorbing substances.

[0127] Examples of lubricants include fatty acid esters, polyethylene waxes (optionally partially saponified), zinc stearate, glyceryl esters, and alkaline earth metal soaps. These lubricants can be used alone or in combination of two or more.

[0128] Regarding the content of lubricant in the foamed particles, from the viewpoint of improving the dispersibility of other additives, it is preferably 0.01% to 1.00% by weight, more preferably 0.05% to 0.50% by weight, and even more preferably 0.10% to 0.30% by weight, relative to 100% of the total amount of polypropylene foamed particles.

[0129] Examples of fillers include silicates, glass fibers, kaolin, wood flour, graphite, graphene, and cellulose nanofibers. These fillers can be used individually or in combination of two or more.

[0130] Regarding the filler content in the foamed granules, for example, relative to 100% by weight of the total amount of the foamed granules, it is preferably 0.01% to 10.00% by weight, more preferably 0.05% to 7.00% by weight, and even more preferably 0.10% to 5.00% by weight.

[0131] To color the resulting foamed molded body in gray or black, the foamed granules may also contain pigments such as carbon black and graphite. Regarding the carbon black content in the foamed granules, from the viewpoints of not impairing flame retardancy and uniform coloring, it is preferably 0.01% to 6.00% by weight, more preferably 0.30% to 4.00% by weight, and even more preferably 0.50% to 3.00% by weight, relative to 100% of the total amount of the foamed granules.

[0132] To further improve the flame retardancy of the obtained foamed molded article, the foamed granules may also contain powdered activated carbon. The content of powdered activated carbon in the foamed granules is preferably 0.8% to 2.8% by weight, more preferably 1.0% to 2.5% by weight, relative to 100% by weight of the total amount of the foamed granules.

[0133] Properties of Polypropylene Foamed Granules

[0134] (Average bubble diameter)

[0135] The average bubble diameter of the foamed particles is not particularly limited, but is preferably 150 μm to 600 μm, more preferably 180 μm to 450 μm, and even more preferably 200 μm to 400 μm. When the average bubble diameter of the foamed particles is (i) 150 μm or more, a foamed molded body with excellent surface aesthetics can be obtained. In addition, when it is (ii) 600 μm or less, the secondary foaming property of the foamed particles during in-mold foaming becomes good, and a foamed molded body with excellent surface aesthetics can be obtained. It can also be said that the average bubble diameter of the foamed particles is the diameter of the pores in the foamed particles.

[0136] It should be noted that in this specification, the method for determining the average bubble diameter of the foamed particles is as follows (1) to (5): (1) Using a razor (e.g., a high-speed stainless steel double-edged razor manufactured by FEATHER), the foamed particle is cut through the center of the foamed particle; (2) Using an optical microscope (VHX-5000 manufactured by Keyence), the cut surface of the obtained foamed particle is observed at a magnification of 50x; (3) In the image obtained by observation, a straight line is drawn through the center or approximately the center of the cut surface of the foamed particle; (4)(4-1) The number of bubbles n present on the straight line is determined; (4-2) Based on the intersection of the straight line and the surface of the foamed particle, the length of the line segment cut from the straight line is determined as the foamed particle diameter L; (5) The average bubble diameter of the foamed particle is calculated using the following formula: average bubble diameter (μm) = L / n.

[0137] (Heat of melting on the high-temperature side of foamed particles)

[0138] The heat of fusion on the high-temperature side of the foamed particles is preferably 5.0 J / g to 25.0 J / g, more preferably 8.0 J / g to 22.0 J / g, and even more preferably 10.0 J / g to 20.0 J / g. When the heat of fusion on the high-temperature side of the foamed particles is (i) 5.0 J / g or higher, it is possible to suppress the occurrence of breakage and dimensional shrinkage at the surface of the foamed molded body during in-mold foaming. When it is 25.0 J / g or lower, it is possible to obtain a foamed molded body with excellent internal weldability and a smooth surface. It can also be said that the heat of fusion on the high-temperature side is the peak heat of fusion on the high-temperature side.

[0139] In this specification, the heat of fusion on the high-temperature side of the foamed particles is measured by the following steps (1) to (5): (1) Measure about 5 mg of foamed particles; (2) Heat the measured foamed particles from 10°C to 190°C at a heating rate of 10°C / min to melt the foamed particles; (3) In the DSC curve of the foamed particles obtained by the process (2) above, connect the point representing the temperature before the start of melting with the point representing the temperature after the end of melting to make a baseline; (4) Draw a straight line perpendicular to the X-axis through the maximum point between the melting peak on the high-temperature side or the melting peak with the highest temperature and the adjacent melting peak; (5) Use the heat (J / g) calculated based on the high-temperature side region surrounded by the baseline, the straight line through the maximum point and the DSC curve as the heat of fusion on the high-temperature side of the foamed particles.

[0140] (Particle weight of foamed granules)

[0141] The particle weight of this foamed granule (the particle weight of each foamed granule) is not particularly limited. From the viewpoint of filling the mold and the surface aesthetics of the resulting foamed molded body, it is preferably 0.5 mg to 10.0 mg, more preferably 0.5 mg to 5.0 mg, and even more preferably 0.5 mg to 2.0 mg relative to one foamed granule.

[0142] In this specification, the particle weight of the foamed granules (the particle weight of each foamed granule) can be determined by, for example, the following steps (1) to (5): (1) Using an electronic balance, determine the weight of 100 randomly sampled foamed granules; (2) Calculate the particle weight of each foamed granule according to the following formula:

[0143] The weight of each foaming granule (mg) = (the weight of 100 foaming granules (mg)) / 100.

[0144] In another embodiment of the present invention, the foamed particles may also be configured as follows: a polypropylene foamed particle comprising 100 parts by weight of polypropylene resin (A), more than 10.0 parts by weight and less than 20.0 parts by weight of organophosphorus compound (B), and 1.0 to 10.0 parts by weight of hindered amine (C).

[0145] [3. Manufacturing method of polypropylene foamed granules]

[0146] A method for manufacturing polypropylene foamed granules according to one embodiment of the present invention includes the following steps: a dispersion step in which polypropylene resin granules, an aqueous dispersion medium and a foaming agent are dispersed in a container; and a release step in which the dispersion obtained by the aforementioned dispersion step is released into a region with a pressure lower than that in the aforementioned container, wherein the aforementioned polypropylene resin granules contain more than 10.0% by weight and less than 20.0% by weight of an organophosphorus compound (B) and 1.0% to 10.0% by weight of hindered amine (C) relative to 100% by weight of the total amount of polypropylene resin granules.

[0147] In this specification, the term "method for manufacturing polypropylene foamed granules according to an embodiment of the present invention" is sometimes referred to as "this manufacturing method".

[0148] (Granulation process)

[0149] In this manufacturing method, a granulation process for preparing polypropylene resin particles may be included before the foaming process. In this specification, "polypropylene resin particles" are sometimes referred to as "resin particles".

[0150] The granulation process in this manufacturing method is not particularly limited as long as it can produce resin particles containing more than 10.0% and less than 20.0% by weight of organophosphorus compound (B) and 1.0% to 10.0% by weight of hindered amine (C) relative to 100% by weight of the total amount of polypropylene resin particles. For example, a method using an extruder can be cited. Specifically, resin particles can be produced by the following methods (1) to (5): (1) a blend is prepared by blending a specified amount of polypropylene resin (A), an organophosphorus compound (B), a hindered amine (C), and other additives as needed; (2) the blend is fed into an extruder and melt-blended to prepare a polypropylene resin composition; (3) the polypropylene resin composition is extruded from a die provided by the extruder; (4) the extruded polypropylene resin composition is cooled by passing it into water or the like, thereby curing it; (5) thereafter, the cured polypropylene resin composition is finely cut into desired shapes such as cylinders, ellipses, spheres, cubes, cuboids, etc., using a cutting machine to obtain polypropylene resin particles. Alternatively, in (3), the melt-blended polypropylene resin composition can be directly extruded from a die provided by the extruder into water, and the polypropylene resin composition can be cut into granular shapes immediately after extrusion, cooled, and cured to obtain resin particles. In this way, by melt-blending the blends, it is possible to obtain more uniform resin particles.

[0151] It should be noted that the ratio of the amounts of polypropylene resin (A), organophosphorus compound (B), and hindered amine (C) contained in the resin particles is the ratio of the amounts of polypropylene resin (A), organophosphorus compound (B), and hindered amine (C) in the blend produced by the aforementioned step (1). Alternatively, it can be described as the ratio of the amounts of polypropylene resin (A), organophosphorus compound (B), and hindered amine (C) contained in the foamed particles. Therefore, regarding the composition of each component of polypropylene resin (A), organophosphorus compound (B), and hindered amine (C) in the resin particles, the descriptions of the <polypropylene resin (A)>, <organophosphorus compound (B)>, and <hindered amine (C)> items above can be appropriately referenced.

[0152] It should be noted that, in order to more uniformly disperse the organophosphorus compound (B) and hindered amine (C) in the resin particles, the organophosphorus compound (B) and hindered amine (C) can be pre-melted using an extruder to prepare a mixture. Alternatively, this mixture, polypropylene resin (A), and other additives as needed can be melt-blended to produce resin particles.

[0153] (Physical properties of polypropylene resin particles)

[0154] (Melting point of resin particles)

[0155] The melting point of the resin particles is not particularly limited, but is preferably 122.0℃ to 159.0℃, more preferably 127.0℃ to 157.0℃, even more preferably 132.0℃ to 151.0℃, even more preferably 135.0℃ to 148.0℃, further preferably 136.0℃ to 145.0℃, and particularly preferably 138.0℃ to 144.0℃. When the melting point of the resin particles is (i) 122.0℃ or higher, a foamed molded body with excellent dimensional stability at high temperatures can be obtained, and when it is (ii) 159.0℃ or lower, an in-mold foamed molded body can be obtained under low water vapor pressure.

[0156] In this specification, the melting point of the resin particles is determined by differential scanning calorimetry (hereinafter referred to as "DSC method"). The specific operating steps are as follows: (1) The resin particles are melted by increasing the temperature of 5 mg to 6 mg of resin particles from 40.0 °C to 220.0 °C at a heating rate of 10.0 °C / min; (2) The melted resin particles are then crystallized by decreasing the temperature of the melted resin particles from 220.0 °C to 40.0 °C at a cooling rate of 10.0 °C / min; (3) The crystallized resin particles are then further heated from 40.0 °C to 220.0 °C at a heating rate of 10 °C / min. The temperature of the peak (melting peak) of the DSC curve of the resin particles obtained at the second heating (i.e., at (3)) can be used as the melting point of the resin particles. It should be noted that when multiple peaks (melting peaks) appear in the DSC curve of the resin particles obtained during the second heating using the above method, the temperature of the peak with the largest heat of fusion (melting peak) is taken as the melting point of the resin particles. As a differential scanning calorimeter, a model such as the Seiko Instruments DSC6200 can be used.

[0157] (Distributed processes)

[0158] The dispersion process can also be described as the process of preparing a dispersion, for example, in an aqueous dispersion medium containing resin particles, a foaming agent, and, as needed, a dispersant and / or dispersing aid.

[0159] The container is not particularly limited, but it is preferably a container that can withstand the foaming temperature and foaming pressure described later. For example, a pressure-resistant container is preferred, and a pressure-resistant container of the autoclave type is more preferred.

[0160] As an aqueous dispersion medium, any medium that can uniformly disperse resin particles, foaming agents, etc., is acceptable; there are no particular limitations. Examples of aqueous dispersion media include (a) dispersion media obtained by adding methanol, ethanol, ethylene glycol, glycerol, etc. to water; and (b) tap water and industrial water, etc. From the viewpoint of stable production of foaming particles, it is preferable to use pure water and ultrapure water such as RO water (water purified using reverse osmosis membrane method), distilled water, deionized water (water purified using ion exchange resin), etc., as an aqueous dispersion medium.

[0161] There is no particular limitation on the amount of aqueous dispersion medium used, but it is preferably 100 to 500 parts by weight relative to 100 parts by weight of resin particles. When the amount of aqueous dispersion medium is (a) 100 parts by weight or more, there is no concern about a decrease in the stability of the dispersion (in other words, the dispersion of the resin particles becomes good), and when it is (b) 500 parts by weight or less, there is no concern about a decrease in productivity.

[0162] Examples of blowing agents include: (a) inorganic gases such as nitrogen, carbon dioxide, and air (a mixture of oxygen, nitrogen, and carbon dioxide), and (a) inorganic blowing agents such as water; and (b) organic blowing agents such as saturated hydrocarbons with 3 to 5 carbon atoms such as propane, n-butane, isobutane, n-pentane, isopentane, and neopentane; (b) ethers such as dimethyl ether, diethyl ether, and methyl ethyl ether; and (b) halogenated hydrocarbons such as monochloromethane, dichloromethane, and dichlorodifluoroethane. At least one blowing agent selected from the group consisting of the above-mentioned inorganic and organic blowing agents can be used. When two or more blowing agents are used in combination, the mixing ratio can be adjusted appropriately according to the purpose. From the viewpoint of environmental impact and foaming power, inorganic blowing agents are preferred among the above-mentioned blowing agents. Furthermore, from the viewpoint of moderately improving the plasticizing effect and easily improving the foaming properties of the foamed particles when manufacturing these foamed particles, the foaming agent is more preferably an inorganic foaming agent containing carbon dioxide, and even more preferably carbon dioxide.

[0163] The amount of foaming agent used is not particularly limited, as long as it is used appropriately according to (a) the type of foaming agent and / or (b) the desired foaming ratio of the foamed particles. The amount of foaming agent used relative to, for example, 1 part to 10,000 parts by weight of resin particles is preferably 1 part to 5,000 parts by weight, and even more preferably 1 part to 1,000 parts by weight. When the amount of foaming agent used is 1 part or more relative to 100 parts by weight of resin particles, foamed particles with suitable density can be obtained. On the other hand, when the amount of foaming agent used is less than 10,000 parts by weight relative to 100 parts by weight of resin particles, an effect consistent with the amount of foaming agent can be obtained, thus avoiding economic waste. The amount of foaming agent used relative to, for example, 100 parts by weight of resin particles can be 1 part to 100 parts by weight, or 1 part to 10 parts by weight.

[0164] When using water as a foaming agent, the water in the dispersion in the container can be used as the foaming agent. Specifically, when using water in the dispersion as a foaming agent, it is preferable to pre-contain a water-absorbing substance in the resin particles. This allows the resin particles to easily absorb the water in the dispersion in the container, thus facilitating the use of water as a foaming agent.

[0165] In this method for manufacturing foamed granules, a dispersant is preferably used. Using a dispersant provides the following advantages: it reduces the adhesion (sometimes called sticking) between resin particles, enabling the stable production of foamed granules. Examples of dispersants include inorganic substances such as tricalcium phosphate, trimagnesium phosphate, basic magnesium carbonate, calcium carbonate, barium sulfate, kaolin, talc, clay, alumina, titanium dioxide, and aluminum hydroxide. These dispersants can be used individually or in combination of two or more. Furthermore, when using two or more dispersants in combination, the mixing ratio can be adjusted appropriately according to the desired effect.

[0166] In one embodiment of the present invention, the amount of dispersant in the dispersion is preferably 0.01 to 3.00 parts by weight relative to 100 parts by weight of resin particles, more preferably 0.05 to 2.00 parts by weight, and even more preferably 0.10 to 1.50 parts by weight. When the amount of dispersant is (a) 0.01 parts by weight or more, there is no concern about poor dispersion of the resin particles; and when it is (b) 3.00 parts by weight or less, there is no concern about poor fusion of the foamed particles when using the obtained foamed particles for in-mold foaming.

[0167] In this method for manufacturing foamed granules, (a) to improve the effect of reducing the adhesion between resin particles and / or (b) to improve the stability of the dispersion in the container, a dispersing agent is preferably used. Examples of dispersing agents include, for instance, anionic surfactants. Examples of anionic surfactants include sodium dodecylbenzene sulfonate (DBS) and other alkylbenzene sulfonates; sodium alkane sulfonate, sodium alkyl sulfonate, sodium alkyl diphenyl ether disulfonate, sodium α-olefin sulfonate, etc. These dispersing agents can be used individually or in combination of two or more. Furthermore, when using two or more dispersing agents in combination, the mixing ratio can be appropriately adjusted according to the purpose.

[0168] In one embodiment of the present invention, the amount of dispersing agent in the dispersion is preferably 0.001 to 0.500 parts by weight, more preferably 0.001 to 0.200 parts by weight, and even more preferably 0.010 to 0.200 parts by weight relative to 100 parts by weight of resin particles. When the amount of dispersing agent is within the aforementioned range, there is no concern about causing poor dispersion of resin particles.

[0169] If the stability of the dispersion decreases, multiple resin particles in the container may adhere to each other or clump together. As a result, sometimes (i) adhered foamed particles are obtained; or (ii) clumps of resin particles remain in the container, making it impossible to produce foamed particles; or (iii) the production rate of foamed particles decreases.

[0170] From the perspectives of (i) further reducing the adhesion between resin particles, enabling more stable production of foamed particles, and (ii) further improving the stability of the dispersion within a container, in this method for manufacturing foamed particles, it is preferable to use tricalcium phosphate and kaolin as dispersants in combination, and sodium dodecylbenzenesulfonate as a dispersing aid. In other words, the dispersion prepared by the dispersion step in this method for manufacturing foamed particles preferably contains tricalcium phosphate, kaolin, and sodium dodecylbenzenesulfonate.

[0171] (Heating-pressurization process and holding process)

[0172] In this manufacturing method, it is preferred that, after the dispersion step and before the release step, the method further includes (i) a temperature-pressure increase step, in which the temperature inside the container is raised to a specified temperature and the pressure inside the container is increased to a specified pressure; and (ii) a holding step, in which the temperature and pressure inside the container are maintained at the specified temperature and specified pressure. The holding step is preferably performed after the temperature-pressure increase step. In this specification, the specified temperature (a) in the temperature-pressure increase step and the holding step is sometimes referred to as the foaming temperature, and the specified pressure (b) is sometimes referred to as the foaming pressure.

[0173] The foaming temperature varies depending on the type of polypropylene resin (A), organophosphorus compound (B), hindered amine (C) contained in the resin particles, and the type of foaming agent, therefore, it cannot be generalized. The preferred foaming temperature is (i) the melting point of a mixture of polypropylene resin (A), organophosphorus compound (B), and hindered amine (C), (b) a polypropylene resin composition, or (c) resin particles, ranging from -20.0°C to +20.0°C; more preferably, it is (ii) the melting point of a mixture of polypropylene resin (A), organophosphorus compound (B), and hindered amine (C), (b) a polypropylene resin composition, or (c) resin particles, ranging from -10.0°C to +15.0°C; and even more preferably, it is (iii) the melting point of a mixture of polypropylene resin (A), organophosphorus compound (B), and hindered amine (C), (b) a polypropylene resin composition, or (c) resin particles, ranging from -5.0°C to +13.0°C.

[0174] The foaming pressure is preferably 0.5 MPa (gauge pressure) to 10.0 MPa (gauge pressure), more preferably 0.6 MPa (gauge pressure) to 5.0 MPa (gauge pressure), and even more preferably 0.6 MPa (gauge pressure) to 2.5 MPa (gauge pressure). If the foaming pressure is 0.5 MPa (gauge pressure) or higher, foamed particles with suitable density can be obtained.

[0175] In the holding process, the time for which the dispersion in the container is held near the foaming temperature and foaming pressure (holding time) is not particularly limited. The holding time is preferably 10 to 60 minutes, more preferably 12 to 50 minutes, and even more preferably 15 to 40 minutes. When the holding time is 10 minutes or more, a sufficient amount of unmelted crystals (polypropylene resin crystals) are present, resulting in the advantage of reducing the shrinkage of the resulting foamed particles and / or the increase in the continuous bubble rate. On the other hand, when the holding time is 60 minutes or less, there is no excessive amount of unmelted crystals, thus providing the advantage of being able to mold the foamed particles at a low molding temperature.

[0176] (Release process)

[0177] Regarding the release process, in (a) where a heating-pressurization process is performed but a holding process is not performed, it is preferable to perform the release process after the heating-pressurization process; in (b) where both the heating-pressurization process and the holding process are performed, it is preferable to perform the release process after the holding process. The release process enables the resin particles to foam, resulting in foamed particles. Alternatively, the release process can be described as opening one end of a container and releasing the dispersion from the container into a region (space) where the pressure is lower than the foaming pressure (i.e., the pressure inside the container).

[0178] In the release process, "the region with pressure lower than the foaming pressure" refers to "the region under pressure lower than the foaming pressure" or "the space under pressure lower than the foaming pressure," or it can be described as "the atmosphere under pressure lower than the foaming pressure." The region with pressure lower than the foaming pressure is not specifically limited as long as the pressure is lower than the foaming pressure; for example, it can be a region under atmospheric pressure.

[0179] During the release process, when releasing the dispersion into a region with a pressure lower than the foaming pressure, the dispersion can be released through an opening with a diameter of 1 mm to 5 mm for purposes such as adjusting the flow rate of the dispersion and reducing the deviation in the foaming ratio of the resulting foamed particles. Alternatively, to improve foaming properties, the aforementioned low-pressure region (space) can be filled with saturated water vapor.

[0180] (Foaming process)

[0181] Sometimes, the process from the dispersion process to the release process is called the foaming process. In addition, the process of making foamed particles from resin particles is called a "single-stage foaming process", and the resulting foamed particles are called "single-stage foamed particles".

[0182] (Two-stage foaming process)

[0183] However, in order to obtain foamed granules with a high expansion ratio, there is a method of increasing the amount of inorganic foaming agent in a single foaming process (hereinafter referred to as Method 1). Furthermore, as a method other than Method 1, the following method can also be used: after obtaining foamed granules (single foamed granules) with a low expansion ratio (approximately 2.0 to 35.0 times) in a single foaming process, the obtained single foamed granules are foamed again, thereby increasing the expansion ratio (hereinafter referred to as Method 2).

[0184] As for the aforementioned Method 2, examples include the following steps (a1) to (a3): (a1) manufacturing a single-stage foaming granule with a foaming ratio of 2.0 to 35.0 times in a single-stage foaming process; (a2) placing the single-stage foaming granule into a pressure-resistant container and pressurizing it at 0.2 MPa (gauge pressure) to 0.6 MPa (gauge pressure) using nitrogen, air, carbon dioxide, etc., thereby increasing the pressure inside the single-stage foaming granule (hereinafter sometimes referred to as "internal pressure") to higher than atmospheric pressure; (a3) ​​subsequently heating the single-stage foaming granule with increased internal pressure using steam, etc., and then foaming it. The process of increasing the foaming ratio of the single-stage foaming granule as in Method 2 is called the "two-stage foaming process," and the polypropylene resin foaming granules obtained by the method of Method 2 are called "two-stage foaming granules."

[0185] In the aforementioned (a3) ​​of the two-stage foaming process, the pressure of the steam used to heat the first-stage foaming particles is preferably adjusted to 0.03 MPa (gauge pressure) to 0.20 MPa (gauge pressure) taking into account the expansion ratio of the second-stage foaming particles. When the steam pressure in the second-stage foaming process is 0.03 MPa (gauge pressure) or higher, there is a tendency to easily increase the expansion ratio; when it is below 0.20 MPa (gauge pressure), the possibility of the resulting second-stage foaming particles sticking together decreases. It should be noted that when the second-stage foaming particles stick together, it is sometimes impossible to supply the resulting second-stage foaming particles for subsequent in-mold foaming molding.

[0186] The internal pressure of the first-stage foamed granules, obtained by impregnating them with nitrogen, air, carbon dioxide, etc., should be appropriately varied considering the expansion ratio of the second-stage foamed granules and the steam pressure of the second-stage foaming process. The internal pressure of the first-stage foamed granules is preferably 0.15 MPa (absolute pressure) to 0.60 MPa (absolute pressure), more preferably 0.20 MPa (absolute pressure) to 0.60 MPa (absolute pressure), and even more preferably 0.30 MPa (absolute pressure) to 0.60 MPa (absolute pressure). When the internal pressure of the first-stage foamed granules is 0.15 MPa (absolute pressure) or higher, high-pressure steam is not required to increase the expansion ratio; therefore, the possibility of adhesion between the second-stage foamed granules is reduced. When the internal pressure of the first-stage foamed granules is 0.6 MPa (absolute pressure) or lower, the possibility of bubble interconnection between the second-stage foamed granules is reduced. As a result, the possibility of a decrease in the compressive strength and other rigidities of the final in-mold foamed molded body is reduced. It should be noted that "bubble interconnection" can also be referred to as "the interconnection of air bubbles."

[0187] [4. Polypropylene-based foamed molding compound]

[0188] The polypropylene-based foamed molded body according to one embodiment of the present invention is a foamed molded body formed by molding the foamed particles (e.g., in-mold foaming). In this specification, "the polypropylene-based foamed molded body according to one embodiment of the present invention" is sometimes referred to as "the foamed molded body".

[0189] This foamed molded body has the above-described structure, and therefore has the advantage of excellent flame retardancy.

[0190] (Flame retardancy of foamed molded parts)

[0191] In this specification, the flame retardancy of the foamed molded articles is evaluated by the oxygen index and UL94 "Vertical Burning Foam Test".

[0192] (Oxygen Index)

[0193] The oxygen index is an indicator of the minimum oxygen concentration (by volume) required for sustained combustion of a material (foamed molded body). Here, "sustainable combustion" means that the burning time of the ignited material is less than 180 seconds and the burning distance is less than 50 mm.

[0194] The oxygen index of this foamed molded body is preferably 26.0% or higher, more preferably 26.5% or higher, and even more preferably 27.0% or higher. It can be said that a foamed molded body with an oxygen index of 26.0% or higher is a foamed molded body with excellent flame retardancy, and also, it can be said to be a foamed molded body with excellent non-flammability. Furthermore, from the perspective of providing a foamed molded body with even better flame retardancy, a higher oxygen index is preferred; there is no particular upper limit to the oxygen index, for example, it can be 45.0% or less or 35.0% or less.

[0195] In this specification, the oxygen index is the value measured according to JIS K7201 (Test method for flammability based on oxygen index).

[0196] (UL94)

[0197] The test method for UL94 “Vertical Burning Foam Material Test” is as follows (1) to (5): (1) Fix the upper part of the test specimen (foamed body) with the desired thickness (sample thickness (t) = 13 mm, 8 mm or 5 mm) with a fixing clamp, hold the test specimen vertically, and place degreased cotton directly below; (2) Contact the lower end of the held test specimen with the flame of the gas burner for 10 seconds to make it burn (first burn); (3) Measure the burning time and red heat time of the test specimen (it should be noted that the flame contact time (10 seconds) is not included in the burning time). If the burning stops within 30 seconds, contact the lower end of the test specimen with the flame of the gas burner again for 10 seconds to make it burn (second burn); (4) Measure the burning time and red heat time of the test specimen again; (5) Change the specimen and repeat the operation of (1) to (4) a total of 5 times, and evaluate the flame retardancy according to the following evaluation criteria.

[0198] Evaluation Criteria

[0199] [Non-compliant (NG)]:

[0200] During the first or second combustion, the sample continues to burn for more than 30 seconds or there are samples that burn until they reach the position of the fixing fixture.

[0201] [V-2]:

[0202] The sample that did not continue to burn for more than 30 seconds after the first contact with the flame;

[0203] The total burning time of the five samples after being exposed to the flame 10 times was less than 250 seconds.

[0204] The sample did not burn until it reached the position of the fixing fixture;

[0205] After the second contact with the flame, no specimen had a combined burning time and red-hot time exceeding 250 seconds; and

[0206] There are samples where the degreased cotton placed below the test sample ignites due to particles falling from the test sample during combustion.

[0207] [V-1]:

[0208] After either the first or second contact with the flame, no sample continued to burn for more than 30 seconds.

[0209] The total burning time of the five samples after being exposed to the flame 10 times was less than 250 seconds.

[0210] The sample did not burn until it reached the position of the fixing fixture;

[0211] After the second contact with the flame, no specimen had a combined burning time and red-hot time exceeding 250 seconds; and

[0212] During any combustion, no test specimen ignited due to falling test specimen particles, and none of the test specimens placed below them did.

[0213] [V-0]:

[0214] After either the first or second contact with the flame, no sample continued to burn for more than 10 seconds.

[0215] The total burning time of the five samples after being exposed to the flame 10 times was less than 50 seconds.

[0216] The sample did not burn until it reached the position of the fixing fixture;

[0217] After the second contact with the flame, no sample had a combined burning time and red-hot time exceeding 30 seconds; and

[0218] During any combustion, no test specimen ignited due to falling test specimen particles, and none of the test specimens placed below them did.

[0219] As described above, no sample of the foamed molded body that meets the V-0 standard has a continuous burning time of more than 10 seconds, and no sample has a burning time and red-hot time that sum to 30 seconds or more after contact with a flame. That is, it can be said to be a molded body with superior flame retardancy compared to foamed molded bodies that only meet V-2 and / or V-1.

[0220] Furthermore, the molded body that meets the V-0 standard will not cause the absorbent cotton placed below the test sample to ignite due to the falling particles of the test sample during any combustion. In other words, it can be said to be a molded body with excellent self-extinguishing properties, which will extinguish the fire before reaching the absorbent cotton (combustible material) even if combustible particles are generated during combustion.

[0221] In other words, it can be said that a foamed molded body that meets V-0 has superior flame retardancy and self-extinguishing properties compared to a foamed molded body that only meets V-2 and / or V-1.

[0222] In this specification, when the flame retardancy is determined and evaluated according to UL94 under all conditions where the thickness of the test specimen is 13 mm, 8 mm or 5 mm, the foamed molded body that meets the benchmark V-0 can be evaluated as a foamed molded body with excellent flame retardancy.

[0223] As described above, under all conditions where the oxygen index of the foamed molded body is (a) 26.0% or higher and / or (b) the thickness of the test specimen is 13 mm, 8 mm, or 5 mm, and the criterion V-0 is met, the foamed molded body can be judged to have excellent flame retardancy. That is, this foamed molded body satisfies (a) and / or (b) above. From the perspective of forming a foamed molded body with even better flame retardancy, this foamed molded body preferably satisfies both (a) and (b) above.

[0224] (Density of foamed molded parts)

[0225] The density of this foamed molded body is preferably 15.0 g / L to 400.0 g / L. If the density of the molded body is 15.0 g / L or higher, it has the advantage of producing a smooth foamed molded body with excellent surface aesthetics, without surface cracking. If it is 400.0 g / L or lower, a sufficiently lightweight foamed molded body can be obtained. Furthermore, the density of this foamed molded body can be (I) 15.0 g / L to 92.0 g / L, or (II) exceeding 92.0 g / L but less than 400.0 g / L. When the density of this foamed molded body is within the range of (I), a foamed molded body with better lightweight and cushioning properties can be obtained. Furthermore, when it is within the range of (II), a foamed molded body with better strength, dimensional stability, and self-extinguishing properties can be obtained.

[0226] It should be noted that, in this specification, the density of the foamed molded body is the value obtained by following steps (1) to (3): (1) Measure the length (mm), width (mm) and thickness (mm) of the foamed molded body and calculate the volume V (L) of the foamed molded body; (2) Measure the weight W (g) of the foamed molded body; (3) Calculate the density of the foamed molded body according to the following formula: density of foamed molded body (g / L) = W / V.

[0227] <Manufacturing Method of Foamed Molded Body>

[0228] The manufacturing method of this foamed molded body is not particularly limited, and known methods can be used. Specific methods for manufacturing this foamed molded body include, for example, the following manufacturing methods (b1) to (b6) in sequence (in-mold foaming molding method), but are not limited to this method:

[0229] (b1) A mold consisting of a stationary, non-driveable type and a movable, driveable type is mounted on an in-mold foaming molding machine. Here, the stationary and movable types are formed by driving the movable type toward the stationary type (sometimes referred to as "mold closing").

[0230] (b2) The moving type is driven toward the fixed type in such a way that the fixed type and the moving type are not fully closed, so as to form a slight gap (also known as a crack);

[0231] (b3) Foamed particles are filled into the molding space formed inside the fixed and movable types by means of, for example, a filling machine;

[0232] (b4) Drive the mobile type in a manner that allows the fixed and mobile types to fully close the mold (i.e., fully close the mold);

[0233] (b5) After preheating the mold with steam, the mold is heated on one side and the opposite side with steam, and then heated on both sides with steam to achieve in-mold foaming molding.

[0234] (b6) Remove the in-mold foamed material from the mold and dry it (e.g., at 75°C) to obtain the foamed body.

[0235] As mentioned above (b3), the following methods (b3-1) to (b3-4) can be listed as methods for filling foamed particles into the molding space:

[0236] (b3-1) A method of pressurizing foamed particles (including the above two-stage foamed particles, the same below) in a container using inorganic gas, so that the inorganic gas permeates into the foamed particles, and then filling the foamed particles into the molding space after applying a specified internal pressure to the foamed particles.

[0237] (b3-2) A method of compressing foamed granules into the molding space by reducing the volume of the mold by 10% to 75%;

[0238] (b3-3) A method of compressing foamed particles using gas pressure and filling them into the molding space;

[0239] (b3-4) A method of filling foamed particles into the molding space without special pretreatment.

[0240] In this method for manufacturing the foamed molded article, the inorganic gas used in the aforementioned method (b3-1) can be at least one selected from the group consisting of air, nitrogen, oxygen, carbon dioxide, helium, neon, argon, etc. Among these inorganic gases, air and / or carbon dioxide are preferred.

[0241] In this method for manufacturing the foamed molded body, the internal pressure of the foamed particles in the aforementioned method (b3-1) is preferably 0.11 MPa (absolute pressure) to 0.40 MPa (absolute pressure), and more preferably 0.13 MPa (absolute pressure).

[0242] ~0.30MPa (absolute pressure).

[0243] In this method for manufacturing a foamed molded body, the temperature inside the container when the inorganic gas in method (b3-1) is impregnated into the foamed particles is preferably 10°C to 90°C, and more preferably 40°C to 90°C.

[0244] In the methods described above (b3-2) and (b3-3), in the subsequent step (b5), the restoring force of the foamed particles compressed by gas pressure is utilized in order to fuse the foamed particles.

[0245] One embodiment of the present invention may be configured as follows.

[0246] [1] A polypropylene foamed granule comprising a polypropylene resin (A), an organophosphorus compound (B) and a hindered amine (C), comprising, relative to 100% by weight of the total amount of the aforementioned polypropylene foamed granule, more than 10.0% by weight and less than 20.0% by weight of the organophosphorus compound (B) and 1.0% to 10.0% by weight of the hindered amine (C).

[0247] [2] The polypropylene foamed particles according to [1], wherein the aforementioned organophosphorus compound (B) is a cyclic phosphonate.

[0248] [3] The polypropylene foamed particles according to [2], wherein the aforementioned cyclic phosphonate is a cyclic bisphosphonate.

[0249] [4] The polypropylene foamed particles according to [3], wherein the aforementioned cyclic bisphosphonate is pentaerythritol bisphosphonate.

[0250] [5] Polypropylene foamed particles according to any one of [1] to [4], wherein the weight ratio (ratio (B) / (C)) of the aforementioned hindered amine (C) to the aforementioned organophosphorus compound (B) is 1.0 to 20.0.

[0251] [6] Polypropylene foamed granules according to any one of [1] to [5], wherein the total amount of the aforementioned organophosphorus compound (B) and the aforementioned hindered amine (C) is in a weight ratio (ratio (A) / {(B)+(C)}) of the aforementioned polypropylene resin (A) to 10.

[0252] [7] Polypropylene foamed particles according to any one of [1] to [6] have two melting peaks in a differential scanning calorimeter determination, with a high-temperature melting heat of 5.0 J / g to 25.0 J / g.

[0253] [8] Polypropylene foamed granules according to any one of [1] to [7], wherein the MI of the aforementioned polypropylene resin (A) is 3.00 g / 10 min to 30.00 g / 10 min.

[0254] [9] Polypropylene foamed particles according to any one of [1] to [8], wherein the aforementioned polypropylene resin (A) is a random copolymer of propylene and monomers other than propylene.

[0255]

[10] The polypropylene foamed particles according to any one of [1] to [9] have an average bubble diameter of 180 μm to 450 μm.

[0256]

[11] The polypropylene foamed granules according to any one of [1] to

[10] have a granule weight of 0.5 mg to 10.0 mg.

[0257]

[12] A polypropylene foamed molded body, which is formed by molding polypropylene foamed particles as described in any one of [1] to

[11] .

[0258]

[13] The polypropylene foamed molded body according to

[12] , wherein the oxygen index of the aforementioned foamed molded body, as measured according to JIS K7201, is 26.0% or more.

[0259]

[14] The polypropylene foamed molding body according to

[12] or

[13] has a density of 15.0 g / L to 92.0 g / L.

[0260]

[15] The polypropylene foamed molded body according to

[12] or

[13] has a density of more than 92.0 g / L and less than 400.0 g / L.

[0261]

[16] A method for manufacturing polypropylene foamed granules, comprising the following steps: a dispersion step in which polypropylene resin granules, an aqueous dispersion medium and a foaming agent are dispersed in a container; and a release step in which the dispersion obtained by the aforementioned dispersion step is released to a region with a pressure lower than that in the aforementioned container, wherein the aforementioned polypropylene resin granules contain more than 10.0% by weight and less than 20.0% by weight of an organophosphorus compound (B) and 1.0% to 10.0% by weight of hindered amine (C) relative to 100% by weight of the total amount of the aforementioned polypropylene resin granules.

[0262]

[17] The method for manufacturing polypropylene foamed particles according to

[16] , wherein the aforementioned dispersion comprises tricalcium phosphate, kaolin and sodium dodecylbenzenesulfonate.

[0263]

[18] Polypropylene foamed granules according to any one of [1] to

[11] , wherein the melting point of the aforementioned polypropylene resin (A) is 125.0°C to 160.0°C.

[0264]

[19] Polypropylene foamed particles according to any one of [1] to

[11] and

[18] , wherein the aforementioned hindered amine (C) has an OR group directly substituted on the N atom.

[0265]

[20] Polypropylene foamed particles according to any one of [1] to

[11] ,

[18] and

[19] , wherein the aforementioned hindered amine (C) contains a triazine component.

[0266]

[21] Polypropylene foamed particles according to any one of [1] to

[11] and

[18] to

[20] , wherein 100% by weight of the total amount of polypropylene foamed particles contains 0.030% to 0.500% by weight of an inorganic nucleating agent.

[0267]

[22] Polypropylene foamed particles according to any one of [1] to

[11] and

[18] to

[21] , wherein the aforementioned hindered amine (C) is a compound with CAS number 191680-81-6 and / or bis(1-undecoxy-2,2,6,6-tetramethylpiperidin-4-yl) carbonate.

[0268] This invention is not limited to the embodiments described above. Various modifications can be made within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments also fall within the technical scope of this invention.

[0269] Example

[0270] The present invention will be specifically described below through embodiments, but the technical scope of the present invention is not limited to these embodiments.

[0271] 〔Material〕

[0272] The following shows the substances used in the examples and comparative examples.

[0273] <Polypropylene Resin (A)>

[0274] Polypropylene (A1): Ethylene-based random polypropylene (ethylene / propylene random copolymer), MI = 7.00 g / 10 min, melting point 144℃, ethylene content 3.2%.

[0275] Polypropylene (A2): Ethylene-based random polypropylene (ethylene / propylene random copolymer), MI = 5.00 g / 10 min, melting point 143℃, ethylene content 3.5%.

[0276] Polypropylene (A3): Ethylene-based random polypropylene (ethylene / propylene random copolymer), MI = 4.00 g / 10 min, melting point 143℃, ethylene content 3.4%.

[0277] Polypropylene (A4): Ethylene-based random polypropylene (ethylene / propylene random copolymer), MI = 6.00 g / 10 min, melting point 143℃, ethylene content 3.4%.

[0278] <Organophosphorus compounds (B)>

[0279] Pentaerythritol diphosphonate: AFLAMMIT (registered trademark) PCO900, manufactured by Thor GmbH.

[0280] <Hindered amine (C)>

[0281] The compound with CAS number 191680-81-6: BASF-manufactured FLAMESTAB (registered trademark) NOR116

[0282] <Other Additives>

[0283] (Inorganic nucleating agent)

[0284] Talc: Talc powder PK-S manufactured by Lin Huacheng Company

[0285] (Antioxidants)

[0286] BASF Corporation Irgafos168

[0287] BASF Irganox 1010

[0288] (UV protection agent)

[0289] BASF company Tinuvin622

[0290] <Foaming Agent>

[0291] Carbon dioxide: manufactured by Air Water Company.

[0292] <Dispersant>

[0293] Kaolin: BASF ASP-170 kaolin

[0294] Tricalcium phosphate: Tricalcium phosphate produced by Taiping Chemical Company

[0295] <Dispersing agents>

[0296] Sodium dodecylbenzenesulfonate: DBS G-15 manufactured by Kao Corporation

[0297] It should be noted that the dispersant and dispersing aid are added to the dispersion or pressure-resistant sealed container in the dispersion process described later, therefore, they will not remain in the resin particles and foamed particles, or will only remain in trace amounts. Furthermore, due to the high gas permeability of the foamed particles, the carbon dioxide used as a blowing agent will be released from the resulting foamed particles. Additionally, water, which functions as a foaming component, will be released from the resulting foamed particles in the form of vapor or evaporate during the drying of the foamed particles. For these reasons, water, blowing agent, dispersant, and dispersing aid are not included in the composition calculation of the foamed particles.

[0298] [Measurement Method]

[0299] The evaluation methods implemented in the embodiments and comparative examples are described below.

[0300] (MI of polypropylene resin (A))

[0301] The MI of polypropylene resin (A) was determined as follows: using the MI measuring instrument described in JIS K7210:1999, the measurement was performed under the following conditions: orifice diameter of 2.0959±0.005mmφ, orifice length of 8.000±0.025mm, load of 2160g, and temperature of 230±0.2℃.

[0302] (Melting point of resin particles)

[0303] The melting point of the resin particles was determined using a differential scanning calorimeter (Seiko Instruments, DSC6200). The specific determination method was as follows (1) to (3): (1) The resin particles were melted by heating 5 mg to 6 mg of resin particles from 40.0 °C to 220.0 °C at a heating rate of 10.0 °C / min; (2) The melted resin particles were then cooled from 220.0 °C to 40.0 °C at a cooling rate of 10.0 °C / min to crystallize the resin particles; (3) The crystallized resin particles were then further heated from 40.0 °C to 220.0 °C at a heating rate of 10 °C / min. The temperature of the peak (melting peak) of the DSC curve of the resin particles obtained at the second heating (i.e., at (3)) was taken as the melting point of the resin particles. It should be noted that when multiple peaks (melting peaks) are present in the DSC curve of the resin particles obtained during the second heating using the above method, the temperature of the peak with the largest heat of fusion (melting peak) shall be taken as the melting point of the resin particles.

[0304] (Determination of the average bubble diameter of foamed particles)

[0305] The method for determining the average bubble diameter of the foamed particles is as follows (1) to (5): (1) Using a razor (a high-speed stainless steel double-edged razor manufactured by FEATHER), the foamed particle is cut through the center; (2) Using an optical microscope (a VHX-5000 manufactured by Keyence), the cut surface of the obtained foamed particle is observed at 50x magnification; (3) In the image obtained by observation, a straight line is drawn through the center or approximately the center of the cut surface of the foamed particle; (4) (4-1) The number of bubbles n present on the straight line is determined; (4-2) Based on the intersection of the straight line and the surface of the foamed particle, the length of the line segment cut from the straight line is determined as the foamed particle diameter L; (5) The average bubble diameter of the foamed particle is calculated using the following formula:

[0306] Average bubble diameter (μm) = L / n.

[0307] (Heat of melting on the high-temperature side of foamed particles)

[0308] The heat of fusion on the high-temperature side of the foamed particles was determined by the following steps (1) to (5): (1) Measure about 5 mg of foamed particles; (2) Heat the measured foamed particles from 10 °C to 190 °C at a heating rate of 10 °C / min to melt the foamed particles; (3) In the DSC curve of the foamed particles obtained by the process (2) above, connect the point representing the temperature before the start of melting with the point representing the temperature after the end of melting to make a baseline; (4) Draw a straight line perpendicular to the X-axis through the maximum point between the melting peak on the high-temperature side or the melting peak with the highest temperature and the adjacent melting peak; (5) Take the heat (J / g) calculated based on the high-temperature side region surrounded by the baseline, the straight line through the maximum point and the DSC curve as the heat of fusion on the high-temperature side of the foamed particles.

[0309] (Density of foamed molded parts)

[0310] The method for determining the density of the foamed molded body (density of the foamed molded body) is as follows (1) to (3): (1) Measure the length (mm), width (mm), and thickness (mm) of the foamed molded body, and calculate the volume V (L) of the foamed molded body; (2) Measure the weight W (g) of the foamed molded body; (3) Calculate the density of the foamed molded body according to the following formula:

[0311] Density of foamed molded material (g / L) = W / V.

[0312] (Flame retardancy of foamed molded parts)

[0313] The flame retardancy of foamed molded materials is determined and evaluated by the oxygen index (OI) and UL94 "Vertical Burning Foamed Materials Test".

[0314] (Oxygen Index)

[0315] The oxygen index of the foamed molded body is determined as follows (1) to (2): (1) a sample with a length of 150 mm × width of 10 mm × thickness of 10 mm is cut from the foamed molded body; (2) the oxygen index of the cut sample is determined according to JIS K7201 (flammability test method based on oxygen index).

[0316] (UL94 "Vertical Burning Foam Material Test")

[0317] The test method for UL94 “Vertical Burning Foam Material Test” is as follows (1) to (5): (1) Cut a test specimen (sample) with specific dimensions (length 125±5mm × width 13±0.5mm) and specific thickness (thickness (t) of the test specimen = 13mm, 8mm or 5mm) from the foam molded body; (2) Fix the upper part of the cut test specimen with a fixing clamp, hold the test specimen vertically, and place degreased cotton directly below it; (3) Contact the lower end of the held test specimen with the flame of the gas burner for 10 seconds to make it burn (first burn); (4) Measure the burning time and red heat time of the test specimen. If the burning stops within 30 seconds, contact the lower end of the test specimen with the flame of the gas burner again for 10 seconds to make it burn (second burn); (5) Measure the burning time and red heat time of the test specimen again; (6) Change the test specimen and repeat the operation of (1) to (4) a total of 5 times, and evaluate the flame retardancy according to the following evaluation criteria.

[0318] Evaluation Criteria

[0319] [Non-compliant (NG)]: A sample that continues to burn for more than 30 seconds during the first or second burn, or a sample that burns until it reaches the position of the fixing fixture.

[0320] [V-2]: Samples that did not continue to burn for more than 30 seconds after the first contact with the flame;

[0321] The total burning time of the five samples after being exposed to the flame a total of 10 times was less than 250 seconds.

[0322] The sample did not burn until it reached the position of the fixing fixture;

[0323] After the second contact with the flame, no specimen had a combined burning time and red-hot time exceeding 250 seconds; and

[0324] There are samples where the degreased cotton placed below the test sample ignites due to particles falling from the test sample during combustion.

[0325] [V-1]: Samples that did not continue burning for more than 30 seconds after either the first or second contact with the flame;

[0326] The total burning time of the five samples after being exposed to the flame a total of 10 times was less than 250 seconds.

[0327] The sample did not burn until it reached the position of the fixing fixture;

[0328] After the second contact with the flame, no specimen had a combined burning time and red-hot time exceeding 250 seconds; and

[0329] During any combustion, no test specimen ignited due to falling test specimen particles, and none of the test specimens placed below them did.

[0330] [V-0]: Samples that did not continue burning for more than 10 seconds after either the first or second contact with the flame;

[0331] The total burning time of the five samples after being exposed to the flame a total of 10 times was less than 50 seconds.

[0332] The sample did not burn until it reached the position of the fixing fixture;

[0333] After the second contact with the flame, no sample had a combined burning time and red-hot time exceeding 30 seconds; and

[0334] During any combustion, no test specimen ignited due to falling test specimen particles, and none of the test specimens placed below them did.

[0335] [Example 1]

[0336] (Preparation of polypropylene resin granules)

[0337] The components were dry-blended in such a manner that the polypropylene resin (A2) accounted for 83.6% by weight, the organophosphorus compound (B) accounted for 11.0% by weight, the hindered amine (C) accounted for 5.0% by weight, and the inorganic nucleating agent talc powder PK-S, the antioxidants Irgafos168 and Irganox1010, and the UV protectant Tinuvin622 accounted for 0.4% by weight in 100% of the blend.

[0338] The resulting blend was fed into a twin-screw extruder [Shibaura Machinery Co., Ltd., TEM26SX] and melt-blended at a resin temperature of 250°C. The melt-blended polypropylene resin composition was extruded in filaments through a die with a circular orifice mounted at the front of the extruder. The extruded polypropylene resin composition was water-cooled and then cut using a cutter to obtain resin granules (granulation process). The melting point of the obtained resin granules was determined. The results are shown in Table 1.

[0339] (Production of polypropylene foamed granules (single-stage foamed granules))

[0340] 100 parts by weight of the obtained resin particles, 442 parts by weight of pure water, 1.1 parts by weight of tricalcium phosphate as a dispersant, 0.22 parts by weight of kaolin ASP-170, and 0.027 parts by weight of DBS as a dispersing aid were added to a pressure-resistant sealed container. Then, while stirring the raw materials in the pressure-resistant sealed container, 2.1 parts by weight of carbon dioxide as a foaming agent were introduced into the aforementioned pressure-resistant sealed container to prepare a dispersion (dispersion step). Next, the temperature inside the pressure-resistant sealed container was heated to a foaming temperature of 150.0°C. Then, carbon dioxide was added to the pressure-resistant sealed container, increasing the pressure inside the container to a foaming pressure of 1.1 MPa (gauge pressure) (heating-pressurization step). Next, after maintaining the pressure-resistant sealed container at the aforementioned foaming temperature and pressure for 20 minutes (holding process), the valve at the bottom of the sealed container is opened, and the dispersion is released through a 3.6 mm orifice into the foaming cylinder at atmospheric pressure, resulting in foamed particles (one stage of foamed particles) (release process). During the release of the dispersion, carbon dioxide is added to the pressure-resistant sealed container to prevent the pressure inside from falling below the foaming pressure, maintaining the pressure inside the pressure-resistant sealed container at 1.1 MPa (gauge pressure). The average bubble diameter and heat of fusion on the high-temperature side of the obtained foamed particles are measured, and the results are shown in Table 1. It should be noted that, relative to 100% by weight of the total amount of the foamed particles, the obtained foamed particles contain 11.0% by weight of organophosphorus compounds (B) and 5.0% by weight of hindered amines (C).

[0341] (Fabrication of polypropylene foamed molded bodies)

[0342] The obtained foamed granules (single-stage foamed granules) were placed into a pressure-resistant sealed container. Air was introduced into the pressure-resistant sealed container, impregnating the foamed granules with pressurized air, thus imparting an internal pressure (absolute pressure) of 0.25 MPa to the foamed granules. Using a molding machine (DAISEN polypropylene in-mold foaming molding machine), the air-impregnated foamed granules were heated and molded with water vapor at 0.32 MPa (gauge pressure) to obtain a foamed molded body. After the obtained foamed molded body was placed at room temperature for 1 hour, it was cured and dried in a constant temperature chamber at 75°C for 12 hours, and then placed at room temperature again for 4 hours. Subsequently, the density and flame retardancy of the obtained foamed molded body were determined and evaluated using the above method. The results are shown in Table 1.

[0343] [Example 2]

[0344] The components were dry-blended in a blend where 81.6% by weight of polypropylene resin (A1), 13.0% by weight of organophosphorus compound (B), and 5.0% by weight of hindered amine (C) were present in 100% by weight of the blend. The foaming temperature was set to 150.9°C and the foaming pressure was set to 1.0 MPa (gauge pressure). Otherwise, resin particles, foamed particles, and foamed molded articles were obtained using the same method as in Example 1, and their physical properties were measured and evaluated. The results are shown in Table 1. It should be noted that the obtained foamed particles contain 13.0% by weight of organophosphorus compound (B) and 5.0% by weight of hindered amine (C) relative to 100% by weight of the total amount of foamed particles.

[0345] [Example 3]

[0346] The components were dry-blended in a blend where 76.6% by weight of polypropylene resin (A3), 15.0% by weight of organophosphorus compound (B), and 8.0% by weight of hindered amine (C) were present in 100% by weight of the blend. The foaming temperature was set to 150.3°C, and the foaming pressure was set to 1.0 MPa (gauge pressure). Otherwise, resin particles, foamed particles, and foamed molded articles were obtained using the same method as in Example 1, and their physical properties were measured and evaluated. The results are shown in Table 1. It should be noted that the obtained foamed particles, relative to 100% by weight of the total amount of foamed particles, contain 15.0% by weight of organophosphorus compound (B) and 8.0% by weight of hindered amine (C).

[0347] [Example 4]

[0348] The components were dry-blended in a blend where 74.6% by weight of polypropylene resin (A3), 20.0% by weight of organophosphorus compound (B), and 5.0% by weight of hindered amine (C) were present in 100% by weight of the blend. The foaming temperature was set to 150.5°C and the foaming pressure was set to 1.2 MPa (gauge pressure). Otherwise, resin particles, foamed particles, and foamed molded articles were obtained using the same method as in Example 1, and their physical properties were measured and evaluated. The results are shown in Table 1. It should be noted that the obtained foamed particles contain 20.0% by weight of organophosphorus compound (B) and 5.0% by weight of hindered amine (C) relative to 100% by weight of the total amount of foamed particles.

[0349] Example 5

[0350] The components were dry-blended in a blend where 81.6% by weight of polypropylene resin (A2), 13.0% by weight of organophosphorus compound (B), and 5.0% by weight of hindered amine (C) were present in 100% by weight of the blend. The foaming temperature was set to 150.2°C, and the foaming pressure was set to 1.5 MPa (gauge pressure). Otherwise, resin particles, foamed particles, and foamed molded articles were obtained using the same method as in Example 1, and their physical properties were measured and evaluated. The results are shown in Table 1. It should be noted that the obtained foamed particles contain 13.0% by weight of organophosphorus compound (B) and 5.0% by weight of hindered amine (C) relative to 100% by weight of the total amount of foamed particles.

[0351] [Example 6]

[0352] The components were dry-blended in a blend where 79.6% by weight of polypropylene resin (A1), 15.0% by weight of organophosphorus compound (B), and 5.0% by weight of hindered amine (C) were present in 100% by weight of the blend. The foaming temperature was set to 151.8°C and the foaming pressure was set to 0.8 MPa (gauge pressure). Otherwise, resin particles, foamed particles, and foamed molded articles were obtained using the same method as in Example 1, and their physical properties were measured and evaluated. The results are shown in Table 1. It should be noted that the obtained foamed particles contain 15.0% by weight of organophosphorus compound (B) and 5.0% by weight of hindered amine (C) relative to 100% by weight of the total amount of foamed particles.

[0353] [Example 7]

[0354] The components were dry-blended in a blend where 79.6% by weight of polypropylene resin (A1), 15.0% by weight of organophosphorus compound (B), and 5.0% by weight of hindered amine (C) were present in 100% by weight of the blend. The foaming temperature was set to 151.9°C and the foaming pressure was set to 0.7 MPa (gauge pressure). Otherwise, resin particles, foamed particles, and foamed molded articles were obtained using the same method as in Example 1, and their physical properties were measured and evaluated. The results are shown in Table 1. It should be noted that the obtained foamed particles contain 15.0% by weight of organophosphorus compound (B) and 5.0% by weight of hindered amine (C) relative to 100% by weight of the total amount of foamed particles.

[0355] [Example 8]

[0356] The components were dry-blended in a blend where 79.6% by weight of polypropylene resin (A1), 15.0% by weight of organophosphorus compound (B), and 5.0% by weight of hindered amine (C) were present in 100% by weight of the blend. The foaming temperature was set to 151.6°C and the foaming pressure was set to 1.0 MPa (gauge pressure). Otherwise, resin particles, foamed particles, and foamed molded articles were obtained using the same method as in Example 1, and their physical properties were measured and evaluated. The results are shown in Table 1. It should be noted that the obtained foamed particles contain 15.0% by weight of organophosphorus compound (B) and 5.0% by weight of hindered amine (C) relative to 100% by weight of the total amount of foamed particles.

[0357] [Example 9]

[0358] The components were dry-blended in a blend where 79.6% by weight of polypropylene resin (A1), 15.0% by weight of organophosphorus compound (B), and 5.0% by weight of hindered amine (C) were present in 100% by weight of the blend. The foaming temperature was set to 151.9°C and the foaming pressure was set to 1.1 MPa (gauge pressure). Otherwise, resin particles, foamed particles, and foamed molded articles were obtained using the same method as in Example 1, and their physical properties were measured and evaluated. The results are shown in Table 1. It should be noted that the obtained foamed particles contain 15.0% by weight of organophosphorus compound (B) and 5.0% by weight of hindered amine (C) relative to 100% by weight of the total amount of foamed particles.

[0359] [Table 1]

[0360]

[0361] [Example 10]

[0362] (Preparation of polypropylene resin granules and polypropylene foamed granules)

[0363] The components were dry-blended in a blend where 79.6% by weight of polypropylene resin (A1), 15.0% by weight of organophosphorus compound (B), and 5.0% by weight of hindered amine (C) were present in 100% by weight of the blend. The foaming temperature was set to 150.3°C, and the foaming pressure was set to 1.2 MPa (gauge pressure). Otherwise, resin particles and foamed particles (single-stage foamed particles) were obtained using the same method as in Example 1, and their physical properties were measured and evaluated. The results are shown in Table 1. It should be noted that the obtained foamed particles contain 15.0% by weight of organophosphorus compound (B) and 5.0% by weight of hindered amine (C) relative to 100% by weight of the total amount of foamed particles.

[0364] (Production of polypropylene foamed granules (two-stage foamed granules))

[0365] After drying the obtained first-stage foamed granules at 60°C for 6 hours, they were placed into a pressure-resistant sealed container. Air was introduced into the pressure-resistant sealed container, impregnating the first-stage foamed granules with pressurized air, thus imposing an internal pressure of 0.30 MPa (absolute pressure) on the first-stage foamed granules. Approximately 20 L of the air-impregnated first-stage foamed granules (imposed internal pressure) was then fed into a foaming machine. Next, the first-stage foamed granules in the foaming machine were heated with water vapor at 0.10 MPa (gauge pressure) for 30 seconds, thereby further foaming the first-stage foamed granules (second-stage foaming), resulting in foamed granules (second-stage foamed granules).

[0366] (Fabrication of polypropylene foamed molded bodies)

[0367] The obtained foamed granules (two-stage foamed granules) were placed into a pressure-resistant sealed container. Otherwise, the foamed molded body was obtained using the same method as in Example 1, and the various physical properties were measured and evaluated. The results are shown in Table 1.

[0368] [Example 11]

[0369] The components were dry-blended in a blend where 74.6% by weight of polypropylene resin (A3), 20.0% by weight of organophosphorus compound (B), and 5.0% by weight of hindered amine (C) were present in 100% by weight of the blend. The foaming temperature was set to 150.5°C and the foaming pressure was set to 1.2 MPa (gauge pressure). Otherwise, resin particles, foamed particles, and foamed molded articles were obtained using the same method as in Example 10, and their physical properties were measured and evaluated. The results are shown in Table 2. It should be noted that the obtained foamed particles contain 20.0% by weight of organophosphorus compound (B) and 5.0% by weight of hindered amine (C) relative to 100% by weight of the total amount of foamed particles.

[0370] [Example 12]

[0371] The components were dry-blended in a blend where 74.6% by weight of polypropylene resin (A3), 20.0% by weight of organophosphorus compound (B), and 5.0% by weight of hindered amine (C) were present in 100% by weight of the blend. The foaming temperature was set to 150.5°C and the foaming pressure was set to 1.2 MPa (gauge pressure). Otherwise, resin particles, foamed particles, and foamed molded articles were obtained using the same method as in Example 1, and their physical properties were measured and evaluated. The results are shown in Table 2. It should be noted that the obtained foamed particles contain 20.0% by weight of organophosphorus compound (B) and 5.0% by weight of hindered amine (C) relative to 100% by weight of the total amount of foamed particles.

[0372] [Example 13]

[0373] The components were dry-blended in a blend where 81.6% by weight of polypropylene resin (A2), 13.0% by weight of organophosphorus compound (B), and 5.0% by weight of hindered amine (C) were present in 100% by weight of the blend. The foaming temperature was set to 148.5°C and the foaming pressure was set to 2.3 MPa (gauge pressure). Otherwise, resin particles, foamed particles, and foamed molded articles were obtained using the same method as in Example 1, and their physical properties were measured and evaluated. The results are shown in Table 2. It should be noted that the obtained foamed particles contain 13.0% by weight of organophosphorus compound (B) and 5.0% by weight of hindered amine (C) relative to 100% by weight of the total amount of foamed particles.

[0374] [Example 14]

[0375] The components were dry-blended in a blend where 81.6% by weight of polypropylene resin (A2), 13.0% by weight of organophosphorus compound (B), and 5.0% by weight of hindered amine (C) were present in 100% by weight of the blend. The foaming temperature was set to 148.5°C and the foaming pressure was set to 2.3 MPa (gauge pressure). Otherwise, resin particles, foamed particles, and foamed molded articles were obtained using the same method as in Example 1, and their physical properties were measured and evaluated. The results are shown in Table 2. It should be noted that the obtained foamed particles contain 13.0% by weight of organophosphorus compound (B) and 5.0% by weight of hindered amine (C) relative to 100% by weight of the total amount of foamed particles.

[0376] [Example 15]

[0377] The components were dry-blended in a blend where 79.6% by weight of polypropylene resin (A1), 15.0% by weight of organophosphorus compound (B), and 5.0% by weight of hindered amine (C) were present in 100% by weight of the blend. The foaming temperature was set to 150.3°C, and the foaming pressure was set to 2.3 MPa (gauge pressure). Otherwise, resin particles, foamed particles, and foamed molded articles were obtained using the same method as in Example 1, and their physical properties were measured and evaluated. The results are shown in Table 2. It should be noted that the obtained foamed particles contain 15.0% by weight of organophosphorus compound (B) and 5.0% by weight of hindered amine (C) relative to 100% by weight of the total amount of foamed particles.

[0378] [Example 16]

[0379] The components were dry-blended in a blend where 79.6% by weight of polypropylene resin (A1), 15.0% by weight of organophosphorus compound (B), and 5.0% by weight of hindered amine (C) were present in 100% by weight of the blend. The foaming temperature was set to 150.3°C, and the foaming pressure was set to 2.3 MPa (gauge pressure). Otherwise, resin particles, foamed particles, and foamed molded articles were obtained using the same method as in Example 1, and their physical properties were measured and evaluated. The results are shown in Table 2. It should be noted that the obtained foamed particles contain 15.0% by weight of organophosphorus compound (B) and 5.0% by weight of hindered amine (C) relative to 100% by weight of the total amount of foamed particles.

[0380] [Example 17]

[0381] The components were dry-blended in a blend where 79.6% by weight of polypropylene resin (A1), 15.0% by weight of organophosphorus compound (B), and 5.0% by weight of hindered amine (C) were present in 100% by weight of the blend. The foaming temperature was set to 150.3°C, and the foaming pressure was set to 2.3 MPa (gauge pressure). Otherwise, resin particles, foamed particles, and foamed molded articles were obtained using the same method as in Example 1, and their physical properties were measured and evaluated. The results are shown in Table 2. It should be noted that the obtained foamed particles contain 15.0% by weight of organophosphorus compound (B) and 5.0% by weight of hindered amine (C) relative to 100% by weight of the total amount of foamed particles.

[0382] [Example 18]

[0383] In a 100% by weight blend, 83.6% by weight of polypropylene resin (A2), 13.0% by weight of organophosphorus compound (B), and 3.0% by weight of hindered amine (C) were dry-blended. The foaming temperature was set to 150.2°C, and the foaming pressure was set to 1.3 MPa (gauge pressure). Otherwise, resin particles, foamed particles, and foamed molded articles were obtained using the same method as in Example 1, and their physical properties were measured and evaluated. The results are shown in Table 2. It should be noted that the obtained foamed particles contain 13.0% by weight of organophosphorus compound (B) and 3.0% by weight of hindered amine (C) relative to 100% by weight of the total amount of foamed particles.

[0384] [Example 19]

[0385] The components were dry-blended in a blend where 81.6% by weight of polypropylene resin (A2), 13.0% by weight of organophosphorus compound (B), and 5.0% by weight of hindered amine (C) were present in 100% by weight of the blend. The foaming temperature was set to 150.2°C, and the foaming pressure was set to 1.5 MPa (gauge pressure). Otherwise, resin particles, foamed particles, and foamed molded articles were obtained using the same method as in Example 1, and their physical properties were measured and evaluated. The results are shown in Table 2. It should be noted that the obtained foamed particles contain 13.0% by weight of organophosphorus compound (B) and 5.0% by weight of hindered amine (C) relative to 100% by weight of the total amount of foamed particles.

[0386] [Table 2]

[0387]

[0388] [Comparative Example 1]

[0389] The components were dry-blended in a blend where 95.6% by weight of polypropylene resin (A1), 2.7% by weight of organophosphorus compound (B), and 1.3% by weight of hindered amine (C) were present in 100% by weight. The foaming temperature was set to 150.7°C, and the foaming pressure was set to 1.7 MPa (gauge pressure). Otherwise, resin particles, foamed particles, and foamed molded articles were obtained using the same method as in Example 1, and their physical properties were measured and evaluated. The results are shown in Table 3. It should be noted that, in addition, the obtained foamed particles contained 2.7% by weight of organophosphorus compound (B) and 1.3% by weight of hindered amine (C) relative to 100% by weight of the total amount of foamed particles.

[0390] [Comparative Example 2]

[0391] The components were dry-blended in a blend where 96.6% by weight of polypropylene resin (A1), 2.7% by weight of organophosphorus compound (B), and 0.3% by weight of hindered amine (C) were present in 100% by weight. The foaming temperature was set to 150.7°C, and the foaming pressure was set to 1.7 MPa (gauge pressure). Otherwise, resin particles, foamed particles, and foamed molded articles were obtained using the same method as in Example 1, and their physical properties were measured and evaluated. The results are shown in Table 3. It should be noted that, in addition, the obtained foamed particles contained 2.7% by weight of organophosphorus compound (B) and 0.3% by weight of hindered amine (C) relative to 100% by weight of the total amount of foamed particles.

[0392] [Comparative Example 3]

[0393] The components were dry-blended with polypropylene resin (A2) comprising 79.6% by weight and organophosphorus compound (B) comprising 20.0% by weight in 100% by weight of the blend. Hindered amine (C) was not used. Other additives totaled 0.4% by weight. The foaming temperature was set to 150.2°C and the foaming pressure to 1.3 MPa (gauge pressure). Otherwise, resin particles, foamed particles, and foamed molded articles were obtained using the same method as in Example 1, and their physical properties were measured and evaluated. The results are shown in Table 3. It should be noted that the obtained foamed particles contain 20.0% by weight of organophosphorus compound (B) relative to 100% by weight of the total amount of the foamed particles.

[0394] [Comparative Example 4]

[0395] The components were dry-blended in a blend where 95.9% by weight of polypropylene resin (A1), 2.7% by weight of organophosphorus compound (B), and 1.0% by weight of hindered amine (C) were present in 100% by weight. The foaming temperature was set to 150.3°C, and the foaming pressure was set to 2.3 MPa (gauge pressure). Otherwise, resin particles, foamed particles, and foamed molded articles were obtained using the same method as in Example 1, and their physical properties were measured and evaluated. The results are shown in Table 3. It should be noted that the obtained foamed particles, relative to 100% by weight of the total amount of foamed particles, contain 2.7% by weight of organophosphorus compound (B) and 1.0% by weight of hindered amine (C).

[0396] [Comparative Example 5]

[0397] The components were dry-blended in a blend where 95.6% by weight of polypropylene resin (A1), 2.7% by weight of organophosphorus compound (B), and 1.3% by weight of hindered amine (C) were present in 100% by weight. The foaming temperature was set to 150.5°C, and the foaming pressure was set to 2.0 MPa (gauge pressure). Otherwise, resin particles, foamed particles, and foamed molded articles were obtained using the same method as in Example 1, and their physical properties were measured and evaluated. The results are shown in Table 3. It should be noted that the obtained foamed particles contain 2.7% by weight of organophosphorus compound (B) and 1.3% by weight of hindered amine (C) relative to 100% by weight of the total amount of foamed particles.

[0398] [Comparative Example 6]

[0399] The components were dry-blended in a blend where 93.6% by weight of polypropylene resin (A1), 4.5% by weight of organophosphorus compound (B), and 1.5% by weight of hindered amine (C) were present in 100% by weight of the blend. The foaming temperature was set to 150.7°C and the foaming pressure was set to 1.7 MPa (gauge pressure). Otherwise, resin particles, foamed particles, and foamed molded articles were obtained using the same method as in Example 1, and their physical properties were measured and evaluated. The results are shown in Table 3. It should be noted that the obtained foamed particles contain 4.5% by weight of organophosphorus compound (B) and 1.5% by weight of hindered amine (C) relative to 100% by weight of the total amount of foamed particles.

[0400] [Comparative Example 7]

[0401] The components were dry-blended in a blend where 85.6% by weight of polypropylene resin (A4), 9.0% by weight of organophosphorus compound (B), and 5.0% by weight of hindered amine (C) constituted 100% by weight of the blend. The foaming temperature was set to 150.5°C, and the foaming pressure was set to 1.4 MPa (gauge pressure). Otherwise, resin particles, foamed particles, and foamed molded articles were obtained using the same method as in Example 1, and their physical properties were measured and evaluated. The results are shown in Table 3. It should be noted that the obtained foamed particles, relative to 100% by weight of the total amount of foamed particles, contain 9.0% by weight of organophosphorus compound (B) and 5.0% by weight of hindered amine (C).

[0402] It should be noted that in all Examples 1-19 and Comparative Examples 1-7, the DSC curves obtained by differential scanning calorimetry (DSC) showed two melting peaks. Furthermore, in all Examples 1-19 and Comparative Examples 1-7, the particle weight of the obtained polypropylene foamed granules was 1.2 mg.

[0403] [Table 3]

[0404]

[0405] 〔Summarize〕

[0406] Based on Tables 1 to 3, the following conclusions can be clearly drawn:

[0407] The oxygen index of the foamed bodies formed from the foamed granules of Examples 1 to 19 was 26.0% or higher. Furthermore, the foamed bodies of Examples 1 to 4 and 6 to 7 met the reference V-0 under all conditions with sample thicknesses of 5 mm, 8 mm, and 13 mm. On the other hand, the oxygen index of the foamed bodies formed from the foamed granules of Comparative Examples 1 to 7 was less than 26.0%, and no foamed body met the reference V-0 under all conditions with sample thicknesses of 5 mm, 8 mm, and 13 mm. As shown above, according to the configuration of this application, a foamed body meeting the reference V-0 can be obtained under all conditions with an oxygen index of 26.0% or higher and / or sample thicknesses of 5 mm, 8 mm, and 13 mm, that is, a foamed body with excellent flame retardancy can be provided.

[0408] Industrial availability

[0409] By in-mold foaming of the polypropylene-based foamed granules according to one embodiment of the present invention, a polypropylene-based foamed molded body with excellent flame retardancy can be provided. The polypropylene-based foamed molded body with excellent flame retardancy can be used in various applications such as cushioning packaging materials, logistics materials, thermal insulation materials, civil engineering components, and automotive components. It is particularly suitable for use in various fields requiring stringent flame retardancy standards, such as transportation, buildings, structures, furniture, electrical equipment, and electronic equipment.

Claims

1. A polypropylene-based foamed granule, comprising a polypropylene resin (A), an organophosphorus compound (B), and a hindered amine (C), wherein the organophosphorus compound (B) is a cyclic phosphonate, and the hindered amine (C) refers to an N-substituted hindered amine having an OR group directly substituted on the N atom, wherein... R is a saturated or unsaturated hydrocarbon group. Relative to 100% by weight of the total amount of the polypropylene foamed particles, it comprises: Organophosphorus compounds (B) exceeding 10.0% by weight and less than 20.0% by weight; and 1.0% to 10.0% by weight of hindered amines (C).

2. The polypropylene foamed granules according to claim 1, wherein, The cyclic phosphonate is a cyclic bisphosphonate.

3. The polypropylene foamed granules according to claim 2, wherein, The cyclic bisphosphonate is pentaerythritol bisphosphonate.

4. Polypropylene foamed granules according to any one of claims 1 to 3, wherein, The weight ratio of the organophosphorus compound (B) to the hindered amine (C), i.e., the ratio (B) / (C), is 1.0 to 20.

0.

5. Polypropylene foamed granules according to any one of claims 1 to 3, wherein, The weight ratio of the polypropylene resin (A) to the total amount of the organophosphorus compound (B) and the hindered amine (C), i.e., the ratio (A) / {(B)+(C)}, is 1 to 10.

6. The polypropylene foamed granules according to any one of claims 1 to 3, which have two melting peaks in the determination based on differential scanning calorimetry, and the heat of melting on the high-temperature side is 5.0 J / g to 25.0 J / g.

7. Polypropylene foamed granules according to any one of claims 1 to 3, wherein, The MI of the polypropylene resin (A) is 3.00 g / 10 min to 30.00 g / 10 min.

8. Polypropylene foamed granules according to any one of claims 1 to 3, wherein, The polypropylene resin (A) is a random copolymer of propylene and monomers other than propylene.

9. The polypropylene foamed granules according to any one of claims 1 to 3, wherein the average bubble diameter is 180 μm to 450 μm and the granule weight is 0.5 mg to 10.0 mg.

10. A polypropylene-based foamed molded body, which is formed by molding polypropylene-based foamed particles according to any one of claims 1 to 9.

11. The polypropylene-based foamed molded article according to claim 10, wherein, The oxygen index of the foamed molded article, as measured according to JIS K7201, is 26.0% or higher.

12. The polypropylene foamed molded body according to claim 10 or 11, wherein the density is 15.0 g / L to 92.0 g / L.

13. The polypropylene foamed molded article according to claim 10 or 11, wherein the density exceeds 92.0 g / L and is less than 400.0 g / L.

14. A method for manufacturing polypropylene foamed granules, comprising the following steps: The dispersion process, which disperses polypropylene resin particles, an aqueous dispersion medium, and a foaming agent in a container; and The release process involves releasing the dispersion obtained through the dispersion process into an area where the pressure is lower than that inside the container. The polypropylene resin particles contain, relative to 100% by weight of total polypropylene resin particles, more than 10.0% by weight and less than 20.0% by weight of organophosphorus compound (B) and 1.0% to 10.0% by weight of hindered amine (C). The organophosphorus compound (B) is a cyclic phosphonate, and the hindered amine (C) refers to an N-substituted hindered amine having an OR group directly substituted on the N atom. R is a saturated or unsaturated hydrocarbon group.

15. The method for manufacturing polypropylene foamed granules according to claim 14, wherein, The dispersion contains tricalcium phosphate, kaolin, and sodium dodecylbenzenesulfonate.

Citation Information

Patent Citations

  • process for the preparation of cyclic esters of phosphonic acid

    FR1503429A

  • Flame-proofing of polyester fibres

    GB1515223A

  • Novel cyclic phosphite esters and process involving transesterification of a phosphite diester with a glycol

    US3152164A

  • Pentaerythrityl diphosphonate-ammonium polyphosphate combinations as flame retardants for olefin polymers

    US4174343A

  • Bi-or tricyclic sterically hindered alkoxyamines and process for their preparation

    US8598369B2